Polarizing film with adhesive layer, image display panel, method for manufacturing image display panel, and adhesive layer
By using an adhesive layer composed of acid groups or anhydride groups and polyether compounds, the problems of reducing the optical characteristics of the polarizing film and reducing the reoperability of the adhesive layer in high temperature environments are solved, and the durability and reusability of the polarizing film are achieved.
Patent Information
- Application Number
- CN202180058953.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-31
- Filing Date
- 2021-06-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-06-17
AI Technical Summary
The polarizing film of the image display device used in a high temperature environment decreases optical characteristics due to large amount of moisture, and the reoperability of the adhesive layer after preheating treatment decreases, which affects the peeling and reuse of the polarizing film.
The adhesive layer consisting of a compound having an acid group or anhydride group and a polyether compound is used to ensure the adhesive force within a specific range by specific heating treatment and testing methods, thereby maintaining the reoperability and durability of the polarizing film.
It realizes the optical properties of the polarizing film and the reoperability of the adhesive layer under a high temperature environment, ensuring the durability and reusability of the polarizing film.
Smart Images

Figure CN116157480B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing film with an adhesive layer, an image display panel, a method for producing an image display panel, and an adhesive layer. Background Art
[0002] The image display panel of an image display device such as a liquid crystal display device has a structure in which a polarizing film is attached to a transparent substrate via an adhesive layer. In order to prevent the image display device from being charged, a conductive layer containing a metal oxide such as indium tin oxide (ITO) is sometimes provided on the surface of the transparent substrate. When a conductive layer is provided on the surface of the transparent substrate, in the image display panel, the adhesive layer is usually directly in contact with the conductive layer.
[0003] When manufacturing an image display panel, for example, a polarizing film with an adhesive layer having an adhesive layer and a polarizing film is pasted to a transparent substrate. At this time, problems may arise such as the pasting position of the polarizing film with an adhesive layer being offset or foreign matter being mixed between the polarizing film with an adhesive layer and the transparent substrate. In this case, in order to improve the productivity of the image display panel, it is desirable to peel the polarizing film with an adhesive layer from the transparent substrate and reuse the component. Therefore, it is required that the polarizing film with an adhesive layer can be easily peeled from the transparent substrate. In this specification, the ease of peeling the polarizing film with an adhesive layer relative to the transparent substrate and the conductive layer is sometimes expressed as "reoperability of the adhesive layer".
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6071459 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In the case where the moisture content of the polarizing film is large, if the image display device is used in a high temperature environment (for example, an environment with a temperature higher than 95°C), there is a tendency for the optical characteristics of the image display device to be reduced (for example, Patent Document 1). The reduction in optical characteristics in a high temperature environment is particularly significant when the polarizer in the polarizing film contains polyvinyl alcohol. Therefore, in the case where it is assumed that the image display device is used in a high temperature environment, for example, when the image display device is used as a vehicle-mounted display, it is necessary to heat the polarizing film with an adhesive layer (preheat) at a temperature of about 70°C to 95°C at the stage of attaching the polarizing film with an adhesive layer to a transparent substrate to reduce the moisture content of the polarizing film in advance.
[0009] However, the polarizing film and the transparent substrate may be damaged due to the preheating. Therefore, it is required that the polarizing film with the adhesive layer can be peeled off from the transparent substrate even after preheating while maintaining the reoperability of the adhesive layer. However, for the adhesive layer in the polarizing film with the adhesive layer, its composition is usually adjusted in a way that improves the adhesion in a high temperature environment. Therefore, when the above-mentioned preheating is performed, there is a tendency that the adhesion of the adhesive layer is improved and the reoperability of the adhesive layer is reduced. According to the research of the inventors, the reoperability is significantly reduced when the adhesive layer is directly in contact with the conductive layer, especially the ITO layer.
[0010] According to the research of the present inventors, if an excessive amount of a compound that improves the reoperability of the adhesive layer is added to the adhesive layer, it may be possible to suppress the reduction in the reoperability of the adhesive layer caused by preheating. However, in this case, there is a tendency that the durability of the adhesive layer is greatly reduced in a high temperature environment.
[0011] Therefore, an object of the present invention is to provide a polarizing film with a pressure-sensitive adhesive layer, which includes a pressure-sensitive adhesive layer that can maintain re-handling properties after preheating even when attached to a conductive layer and has durability in a high-temperature environment.
[0012] Solutions to the problem
[0013] The present invention provides a polarizing film with an adhesive layer, comprising:
[0014] Polarizing film, and
[0015] an adhesive layer formed from the adhesive composition,
[0016] The adhesive composition comprises: a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D),
[0017] The adhesive force P of the above-mentioned adhesive layer was obtained by the following test 1. 85 The adhesive force P obtained by the following test 2 is 10.0 N / 25 mm or less. 105 Greater than 10.0N / 25mm,
[0018] Test 1: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 85°C for 5 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 85 ),
[0019] Test 2: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 105°C for 24 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 105 ).
[0020] In addition, the present invention provides an image display panel, comprising:
[0021] The above-mentioned polarizing film with an adhesive layer,
[0022] a conductive layer comprising a metal oxide, and
[0023] transparent substrate,
[0024] Wherein, the adhesive layer is directly in contact with the conductive layer.
[0025] In addition, the present invention provides a method for manufacturing an image display panel, which is the method for manufacturing the above-mentioned image display panel, and the method comprises:
[0026] The pressure-sensitive adhesive layer is subjected to a first heat treatment at 70° C. to 95° C. in a state where the pressure-sensitive adhesive layer-attached polarizing film is attached to the conductive layer.
[0027] In addition, the present invention provides an adhesive layer formed from the adhesive composition.
[0028] The adhesive composition comprises: a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D),
[0029] The adhesive force P obtained by the following test 1 85 The adhesive force P obtained by the following test 2 is 10.0 N / 25 mm or less. 105 Greater than 10.0N / 25mm,
[0030] Test 1: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 85°C for 5 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 85 ),
[0031] Test 2: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 105°C for 24 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 105 ).
[0032] Effects of the Invention
[0033] According to the present invention, it is possible to provide a polarizing film with a pressure-sensitive adhesive layer that includes a pressure-sensitive adhesive layer that maintains reworkability after preheating even when attached to a conductive layer and has durability in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a cross-sectional view of a pressure-sensitive adhesive layer-attached polarizing film according to one embodiment of the present invention.
[0035] Figure 2 This is a diagram for explaining the characteristics of the pressure-sensitive adhesive layer included in the pressure-sensitive adhesive layer-attached polarizing film.
[0036] Figure 3 This is a cross-sectional view of an image display panel according to one embodiment of the present invention.
[0037] Figure 4 It is a cross-sectional view showing a modified example of the image display panel. DETAILED DESCRIPTION
[0038] Hereinafter, the present invention will be described in detail, but the gist of the following description is not to limit the present invention to specific embodiments.
[0039] (Embodiments of Polarizing Film with Adhesive Layer)
[0040] like Figure 1 As shown, the pressure-sensitive adhesive layer-attached polarizing film 10 of the present embodiment includes a pressure-sensitive adhesive layer 1 and a polarizing film 2. The pressure-sensitive adhesive layer 1 is, for example, directly in contact with the polarizing film 2. The surface of the pressure-sensitive adhesive layer 1 is, for example, exposed to the outside of the pressure-sensitive adhesive layer-attached polarizing film 10.
[0041] In the polarizing film 10 with an adhesive layer, the adhesive force P obtained by Test 1 for the adhesive layer 1 is 85 The adhesive force P obtained by test 2 is 10.0N / 25mm or less. 105 Greater than 10.0N / 25mm.
[0042] Test 1 is carried out by the following method. First, the polarizing film 10 with an adhesive layer is cut into a strip of 150 mm in length and 25 mm in width as a test piece. Next, glass with an indium tin oxide (ITO) layer is prepared. The glass with the ITO layer has, for example, alkali-free glass and an ITO layer in contact with the alkali-free glass. Alkali-free glass is glass that does not substantially contain alkali components (alkali metal oxides). Specifically, the weight ratio of the alkali components in the glass is, for example, less than 1000 ppm, and further less than 500 ppm. The alkali-free glass is, for example, in the form of a plate and has a thickness of more than 0.5 mm. The ITO layer is, for example, substantially formed only of amorphous ITO. However, the ITO layer may contain impurities other than ITO. The ITO layer can be formed on the surface of the alkali-free glass by, for example, a physical deposition method such as a sputtering method.
[0043] Next, the test piece is adhered to the surface of the ITO layer of the glass with the ITO layer through the adhesive layer 1. The adhesion of the test piece to the ITO layer is carried out, for example, using a laminator, so that bubbles are not mixed between the ITO layer and the adhesive layer 1. After the test piece is adhered, it is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the ITO layer and the adhesive layer 1, so that the adhesive layer 1 is closely attached to the ITO layer. Next, the test piece (adhesive layer 1) is heated for 5 hours in an atmospheric pressure atmosphere at 85°C. Next, the test piece is placed in an atmosphere at room temperature (for example, 23°C) to lower the temperature of the test piece to room temperature. The test piece is peeled off from the ITO layer at a peeling speed of 300mm / min and a peeling angle of 90° (measured length 80mm). At this time, the force required to peel the test piece from the ITO layer is measured at intervals of 1 time / 0.5s. The average value of the measured values obtained is designated as the adhesion force P 85 .
[0044] Test 2 was conducted in the same manner as Test 1, except that a heat treatment was performed in an autoclave at 105° C. atmospheric pressure atmosphere for 24 hours to homogenize the bonding between the ITO layer and the adhesive layer 1 .
[0045] According to the research of the present inventors, the adhesive force P 85 When the adhesive force P is 10.0 N / 25 mm or less, the re-workability of the pressure-sensitive adhesive layer 1 tends to be sufficiently maintained after preheating. 85 It is preferably 9.0 N / 25 mm or less, more preferably 8.0 N / 25 mm or less, further preferably 7.0 N / 25 mm or less, and particularly preferably 6.0 N / 25 mm or less. 85 The lower limit value is, for example, 3.0 N / 25 mm.
[0046] According to the research of the present inventors, the adhesive force P105 When the adhesive force P is greater than 10.0 N / 25 mm, the adhesive layer 1 tends to have sufficient durability in a high temperature environment. 105 It is preferably 11.0 N / 25 mm or more, more preferably 12.0 N / 25 mm or more, further preferably 13.0 N / 25 mm or more, and particularly preferably 14.0 N / 25 mm or more. 105 The upper limit of is not particularly limited, and is, for example, 30.0 N / 25 mm.
[0047] In addition, in the polarizing film 10 with an adhesive layer, the adhesive force P0 obtained by Test 3 for the adhesive layer 1 can be 10.0N / 25mm or less. Test 3 can be performed in the same manner as Test 1, except that the bonding between the ITO layer and the adhesive layer 1 is homogenized in an autoclave without heat treatment. The adhesive force P0 is preferably 9.0N / 25mm or less, more preferably 8.0N / 25mm or less, further preferably 7.0N / 25mm or less, and particularly preferably 6.0N / 25mm or less. From a practical point of view, the lower limit of the adhesive force P0 is, for example, 3.0N / 25mm.
[0048] [Adhesive layer]
[0049] The adhesive layer 1 is formed from an adhesive composition. The adhesive composition includes a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D), and further includes, for example, a base polymer. The "base polymer" is, for example, a polymer with the largest content by weight in the adhesive composition, and functions as a component that contributes to the adhesiveness of the adhesive layer 1.
[0050] <Compound (C)>
[0051] Compound (C) is, for example, a low molecular weight compound or an oligomer. The acidic group possessed by compound (C) is, for example, a carboxyl group or a thiol group, preferably a carboxyl group. The acidic group of compound (C) may be a group generated by hydrolysis of an acid anhydride group. Specific examples of the acid anhydride group include carboxylic anhydride groups such as succinic anhydride group, phthalic anhydride group, and maleic anhydride group, preferably a succinic anhydride group. The total value of the content of the acidic group in compound (C) and the content of the acid anhydride group is not particularly limited, and is, for example, 5.0 wt% to 50 wt%, preferably 8.3 wt% to 40 wt%.
[0052] Compound (C) may contain silicon atoms, and may further contain a hydrolyzable group (h1) bonded to the silicon atom. The hydrolyzable group (h1) may, for example, form a siloxane bond by a hydrolysis reaction and / or a condensation reaction. Examples of the hydrolyzable group (h1) include halogen atoms, alkoxy groups, acyloxy groups, alkenyloxy groups, carbamoyl groups, amino groups, amino groups, aminooxy groups, ketoxime groups, and the like. When the hydrolyzable group (h1) has carbon atoms, the number of carbon atoms is, for example, 10 or less, preferably 6 or less, and more preferably 4 or less. Particularly preferred are alkoxy or alkenyloxy groups having 4 or less carbon atoms, and particularly preferred are methoxy or ethoxy groups. The content of the hydrolyzable group (h1) in compound (C) is, for example, 10 wt% or more, preferably 13 wt% to 50 wt%, and more preferably 13 wt% to 49 wt%.
[0053] The compound (C) may contain other functional groups in addition to the acidic group, the acid anhydride group and the hydrolyzable group (h1), but preferably does not contain them. As an example, the compound (C) does not contain a polyether group.
[0054] Compound (C) includes, for example, at least one selected from an alkoxysilane compound (S1) having an acidic group or an acid anhydride group, an organopolysiloxane compound (S2) having an acidic group or an acid anhydride group, and hydrolysis condensates thereof, and preferably includes an organopolysiloxane compound (S2).
[0055] The alkoxysilane compound (S1) is represented by, for example, the following formula (1).
[0056] R 1 R 2 a Si(OR 3 ) 3-a (1)
[0057] In formula (1), R 1 It is an organic group having 1 to 20 carbon atoms and having an acidic group or an acid anhydride group. The organic group may be linear, branched, or cyclic. 2 Each of R is independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 3 Each of the groups is independently an alkyl group having 1 to 10 carbon atoms, preferably a methyl group or an ethyl group.
[0058] From the viewpoint of the availability of the alkoxysilane compound (S1), R 1 An organic group represented by the following formula (2) is preferred.
[0059] [Chemical formula 1]
[0060]
[0061] In formula (2), A is preferably a linear or branched alkylene or alkenylene group having 2 to 10 carbon atoms, or a linear or branched alkylene group having 2 to 6 carbon atoms. Specific examples of A include ethylene and propane-1,3-diyl.
[0062] Examples of the alkoxysilane compound (S1) include 2-trimethoxysilylethylsuccinic anhydride, 3-trimethoxysilylpropylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-12-967C"), 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.
[0063] The organopolysiloxane compound (S2) is a compound having a siloxane bond, and contains, for example, a siloxane unit (U1) represented by the following formula (3). The organopolysiloxane compound (S2) may further contain a siloxane unit (U2) represented by the following formula (4).
[0064] [Chemical formula 2]
[0065]
[0066] [Chemical formula 3]
[0067]
[0068] In formula (3), X is an organic group having an acidic group or an acid anhydride group, preferably an organic group represented by formula (2). 4 R is independently a hydrogen atom, an alkoxy group having 1 to 10 carbon atoms, or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 4 The alkoxy group of R is preferably a methoxy group or an ethoxy group. 4 The hydrocarbon group is, for example, methyl.
[0069] The number of siloxane units (U1) contained in the organopolysiloxane compound (S2) is not particularly limited, and is, for example, 1 to 100, preferably 1 to 50, and more preferably 1 to 20. The number of siloxane units (U2) contained in the organopolysiloxane compound (S2) is not particularly limited, and is, for example, 0 to 100, preferably 0 to 50, and more preferably 0 to 20. The organopolysiloxane compound (S2) preferably contains at least one siloxane unit (U2).
[0070] The organopolysiloxane compound (S2) may have a structure in which at least one siloxane unit (U1) is inserted between O-Si bonds contained in the alkoxysilane represented by the following formula (5) or its partially hydrolyzed condensate. Both the siloxane unit (U1) and the siloxane unit (U2) may be inserted between the O-Si bonds. Among the plurality of O-Si bonds, the siloxane unit (U1) may be inserted between some of the O-Si bonds, and the siloxane unit (U2) may be inserted between other O-Si bonds.
[0071] R 5 n Si(OR 6 ) 3-n (5)
[0072] In formula (5), R 5 Each of R is independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom. 6 Each of the groups is independently an alkyl group having 1 to 10 carbon atoms. n is 0 or 1.
[0073] Examples of the alkoxysilane represented by formula (5) or its partial hydrolysis condensate include tetramethoxysilane, methyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, and compounds obtained by partial hydrolysis condensation of one or more of these alkoxysilanes.
[0074] The organopolysiloxane compound (S2) can be produced by a known production method described in, for example, JP-A-2013-129809 and JP-A-2013-129691.
[0075] As long as the compound (C) has an acidic group or an anhydride group, it is not limited to the above-mentioned alkoxysilane compound (S1) and the organopolysiloxane compound (S2). The compound (C) may contain a (meth) acrylic oligomer (B) having an acidic group or an anhydride group. The (meth) acrylic oligomer (B) contains, for example, a structural unit derived from an alkyl (meth) acrylate as a main component, and contains a structural unit derived from a (meth) acrylic ester having an acidic group or an anhydride group. In this specification, "(meth) acrylic ester" refers to acrylic ester and / or methacrylic ester. "Main component" refers to the structural unit that contains the most in the polymer on a weight basis.
[0076] Examples of the (meth)acrylic acid alkyl ester constituting the (meth)acrylic acid oligomer (B) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Examples of the (meth)acrylate having an acidic group include carboxyl group-containing (meth)acrylates such as (meth)acrylic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate.
[0077] As other monomers constituting the (meth)acrylic oligomer (B), for example, there can be mentioned: esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentadienyl (meth)acrylate; aromatic (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; (meth)acrylates obtained from terpene compound derivative alcohols; (meth)acrylates containing ether bonds such as methoxyethyl (meth)acrylate and phenoxyethyl (meth)acrylate. Such (meth)acrylates can be used alone or in combination of two or more. As monomers constituting the (meth)acrylic oligomer (B), monomers constituting the (meth)acrylic polymer (A) described later can also be used.
[0078] As the polymerization method of the (meth)acrylic oligomer (B), similar to the (meth)acrylic polymer (A) described later, examples thereof include solution polymerization, emulsion polymerization, bulk polymerization, emulsion polymerization, polymerization by heat or active energy ray irradiation (thermal polymerization, active energy ray polymerization), etc. Among them, solution polymerization and active energy ray polymerization are preferred in view of transparency, water resistance, cost, etc. The obtained (meth)acrylic oligomer (B) may be any copolymer such as a random copolymer, a block copolymer, a graft copolymer, etc.
[0079] From the viewpoint of improving the durability, corrosion resistance and reworkability of the adhesive layer 1, in the adhesive composition, the content of the compound (C) is preferably 0.05 to 10 parts by weight, more preferably 3 parts by weight or less, further preferably 2 parts by weight or less, particularly preferably 1 part by weight or less, and most preferably 0.6 parts by weight or less, relative to 100 parts by weight of the base polymer described later. The content of the compound (C) is more preferably 0.1 parts by weight or more, further preferably 0.2 parts by weight or more, and particularly preferably 0.4 parts by weight or more relative to 100 parts by weight of the base polymer.
[0080] The weight average molecular weight of compound (C) is not particularly limited, and is, for example, 10,000 or less, preferably 8,000 or less, more preferably 5,000 or less, further preferably 3,000 or less, and particularly preferably 1,500 or less. The lower limit of the weight average molecular weight of compound (C) is not particularly limited, and is, for example, 100.
[0081] Compound (C) is derived from an acidic group and may have a relatively low acid dissociation constant pKa. The pKa (particularly the first acid dissociation constant) of compound (C) is, for example, 12 or less, preferably 11 or less, more preferably 8 or less, further preferably 6 or less, and particularly preferably 5 or less. The lower limit of the pKa of compound (C) is not particularly limited, and is, for example, 1. In this specification, pKa is a value in water at 25°C.
[0082] <Polyether compound (D)>
[0083] The polyether compound (D) is a compound having a polyether skeleton. The polyether skeleton may be linear or branched. The polyether skeleton of the polyether compound (D) includes, for example, an oxyalkylene unit (U3) represented by the following formula (6).
[0084] [Chemical formula 4]
[0085]
[0086] In formula (6), R 7 is a linear or branched alkylene group having 1 to 10 carbon atoms. 7 The number of carbon atoms is preferably 2 to 6, more preferably 3. The polyether compound (D) may contain one or more oxyalkylene units (U3). The polyether compound (D) may be a random copolymer or a block copolymer. Specific examples of the oxyalkylene unit (U3) include oxyethylene, oxypropylene, oxybutylene, etc. From the perspective of ease of material manufacture, material stability, etc., the oxyalkylene unit (U3) is preferably an oxypropylene group (particularly -CH2CH(CH3)O-).
[0087] The polyether compound (D) may contain silicon atoms and may further contain a hydrolyzable group (h2) bonded to the silicon atom. The hydrolyzable group (h2) may, for example, form a siloxane bond by a hydrolysis reaction and / or a condensation reaction. Examples of the hydrolyzable group (h2) include halogen atoms, alkoxy groups, acyloxy groups, alkenyloxy groups, carbamoyl groups, amino groups, amino groups, aminooxy groups, ketoxime groups, and the like. When the hydrolyzable group (h2) has a carbon atom, the number of carbon atoms is, for example, 10 or less, preferably 6 or less, and more preferably 4 or less. Alkoxy or alkenyloxy groups having a carbon number of 4 or less are particularly preferred, and methoxy or ethoxy groups are particularly preferred. The content of the hydrolyzable group (h2) in the polyether compound (D) is, for example, 14 wt% or less, preferably less than 13 wt%, and more preferably less than 10 wt%. The lower limit of the content of the hydrolyzable group (h2) is not particularly limited, and may be, for example, 2.0 wt%, 2.5 wt%, or 3.0 wt%. The content of the hydrolyzable group (h2) may be 2.0 wt % or less in some cases.
[0088] The hydrolyzable group (h2) bonded to the silicon atom is located, for example, at the terminal of the polyether compound (D). As one example, the polyether compound (D) has a reactive silyl group (b) represented by the following formula (7) at at least one terminal.
[0089] -SiR 8 a M 3-a (7)
[0090] In formula (7), R 8 Each of R is independently a monovalent organic group having 1 to 20 carbon atoms which may have a substituent. 8 Preferably, it is a linear or branched alkyl group having 1 to 8 carbon atoms, a fluoroalkyl group having 1 to 8 carbon atoms, or a phenyl group, more preferably an alkyl group having 1 to 6 carbon atoms, and particularly preferably a methyl group. 8 In the case of multiple R 8 They may be the same or different. M is independently a hydroxyl group or a hydrolyzable group (h2). When a plurality of M are present in the polyether compound (D), the plurality of M may be the same or different. a is an integer of 0 to 2.
[0091] The polyether compound (D) has, for example, at least one reactive silyl group (b) per molecule at its terminal. When the polyether compound (D) is linear, the polyether compound (D) may have one or two reactive silyl groups (b) at its terminal, preferably two reactive silyl groups (b). When the polyether compound (D) is branched, the polyether compound (D) has at least one reactive silyl group (b) at the terminal of the main chain or the terminal of the side chain. The number of reactive silyl groups (b) can be appropriately adjusted according to the number of terminals of the polyether compound (D), preferably two or more, and may be three or more.
[0092] The polyether compound (D) preferably has a reactive silyl group (b) at at least a part of its molecular terminal, and has at least 1, preferably 1.1 to 5, more preferably 1.1 to 3 reactive silyl groups (b) in the molecule.
[0093] The reactive silyl group (b) is preferably an alkoxysilyl group (b1) represented by the following formula (8) or an alkoxysilyl group (b2) represented by the following formula (9).
[0094] [Chemical formula 5]
[0095]
[0096] [Chemical formula 6]
[0097]
[0098] In formula (8) and formula (9), R 9 , R 10 and R 11 Each of them is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms, for example, a linear or branched alkyl group having 1 to 6 carbon atoms, a linear or branched alkenyl group having 2 to 6 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, a phenyl group, etc. As -OR in formula (8) and formula (9): 9 、-OR 10 AND-OR 11 Specific examples include methoxy, ethoxy, propoxy, propenyloxy, phenoxy and the like, preferably methoxy and ethoxy, and particularly preferably methoxy.
[0099] The polyether compound (D) preferably has a main chain substantially composed of a polyether skeleton except for the reactive silyl group (b). However, the main chain of the polyether compound (D) may also contain other chemical structures in small amounts. Examples of other chemical structures include: a chemical structure derived from an initiator for forming an oxyalkylene unit (U3), and a linking group between a polyether skeleton and a reactive silyl group (b). The content of the oxyalkylene unit (U3) in the polyether compound (D) is preferably 50% by weight or more, more preferably 80% by weight or more.
[0100] The polyether compound (D) is represented by, for example, the following formula (10).
[0101] R 12 a M 3-a Si-XY-(AO) n -Z(10)
[0102] In formula (10), R 12 Each of them is independently a monovalent organic group having 1 to 20 carbon atoms and optionally having a substituent. Each of M is independently a hydroxyl group or a hydrolyzable group (h2). a is an integer of 0 to 2. AO is a linear or branched oxyalkylene group having 1 to 10 carbon atoms. n represents the average number of added moles of the oxyalkylene group, which is 1 to 1700. X is a linear or branched alkylene group having 1 to 20 carbon atoms. Y is an ether bond, an ester bond, a carbamate bond, or a carbonate bond. Z is a hydrogen atom, a monovalent hydrocarbon group having 1 to 10 carbon atoms, a group represented by the following formula (11), or a group represented by the following formula (12).
[0103] -Y 1 -X-SiR 12 a M 3-a (11)
[0104] -Q{-(OA) n -YX-SiR 12 a M 3-a} m (12)
[0105] In formula (11), R 12 , M and X are the same as those in formula (10). 1 is a single bond, a -CO- bond, a -CONH- bond or a -COO- bond. In formula (12), R 12 , M, X, Y and n are the same as those in formula (10). OA is the same as AO in formula (10). Q is a divalent or higher hydrocarbon group having 1 to 10 carbon atoms. m is a value obtained by subtracting 1 from the valence of the hydrocarbon group of Q.
[0106] X in the formula (10) is a linear or branched alkylene group having 1 to 20 carbon atoms. The alkylene group preferably has 2 to 10 carbon atoms, more preferably 3 carbon atoms.
[0107] Y in the formula (10) is a bond formed by reaction with a hydroxyl group of an oxyalkylene group at the terminal of a polyether skeleton, and is preferably an ether bond or a urethane bond, and more preferably a urethane bond.
[0108] Z is, for example, a hydroxy compound used in the preparation of the polyether compound (D) represented by formula (10), which is an initiator in the synthesis of the oxyalkylene polymer. Z is, for example, a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. In this case, the polyether compound (D) represented by formula (10) has one reactive silyl group (b) at its end. When Z is a hydrogen atom, it is equivalent to the case where the same structural unit as the oxyalkylene polymer is used as the hydroxy compound. When Z is a monovalent hydrocarbon group having 1 to 10 carbon atoms, it is equivalent to the case where a hydroxy compound having one hydroxyl group is used.
[0109] On the other hand, when Z is represented by formula (11) or formula (12), the polyether compound (D) has a plurality of reactive silyl groups (b) at its terminal. When Z is represented by formula (11), it is equivalent to the case where the same constituent unit as the oxyalkylene polymer is used as the hydroxyl compound. When Z is represented by formula (12), it is equivalent to the case where a hydroxyl compound having two hydroxyl groups and different from the constituent unit of the oxyalkylene polymer is used. It should be noted that Y in formula (11) 1 Similar to Y in formula (10), it is a bond formed by reaction with the hydroxyl group of the oxyalkylene group at the terminal of the polyether skeleton.
[0110] From the viewpoint of re-operability, the polyether compound (D) is preferably represented by the following formula (13), formula (14) or formula (15).
[0111] Z 0 -A 2 -O-(A 1 O) n -Z 1 (13)
[0112] Z 0 -A 2 -NHCOO-(A 1 O) n -Z 2 (14)
[0113] Z 3 -O-(A 1 O) n -CH{-CH2-(A 1 O)n -Z 3}2 (15)
[0114] In formulas (13) to (15), Z 0 is an alkoxysilyl group represented by formula (8) or formula (9). 1 O is an oxyalkylene group having 2 to 6 carbon atoms, and is preferably an oxypropylene group. 1 The oxyalkylene group represented by O may be linear or branched. 1 The average number of moles of O added is 1 to 1700. A in formula (13) and formula (14) 2 A is an alkylene group having 2 to 6 carbon atoms, preferably a propylene group. 2 The alkylene group may be linear or branched. 1 A hydrogen atom or -A 2 -Z 0 . Z in formula (14) 2 A hydrogen atom or -CONH-A 2 -Z 0 . Z in formula (15) 3 A hydrogen atom or -A 2 -Z 0 , at least 1 Z 3 For-A 2 -Z 0 .
[0115] As the compound represented by the formula (14), for example, a compound represented by the following formula (16) is preferred.
[0116] [Chemical formula 7]
[0117]
[0118] In formula (16), R 9 , R 10 and R 11 Each of them is independently a monovalent hydrocarbon group having 1 to 6 carbon atoms. n represents the average number of moles of oxypropylene groups added, and is 1 to 1700. 21 It is a hydrogen atom or a trialkoxysilyl group represented by the following formula (17).
[0119] [Chemical formula 8]
[0120]
[0121] In formula (17), R 9 , R 10 and R 11 Same as formula (16).
[0122] From the perspective of reoperability, the number average molecular weight of the polyether compound (D) is preferably 300 to 100,000. The number average molecular weight is preferably 500 or more, further 1,000 or more, further 2,000 or more, further 3,000 or more, further 4,000 or more, further 5,000 or more, and is preferably 50,000 or less, further 40,000 or less, further 30,000 or less, further 20,000 or less, further 10,000 or less. n (the average number of added moles of oxyalkylene groups in the polyether skeleton) in the above formulas (10) to (16) is appropriately adjusted, for example, so that the number average molecular weight of the polyether compound (D) is within the above range. When the number average molecular weight of the polyether compound (D) is 1,000 or more, the above n is usually 10 to 1,700.
[0123] The Mw (weight average molecular weight) / Mn (number average molecular weight) of the polyether compound (D) is preferably 3.0 or less, more preferably 1.6 or less, and particularly preferably 1.5 or less. In order to obtain a polyether compound (D) having a small Mw / Mn, it is preferred to use a method in which a cyclic ether is polymerized in the presence of an initiator using the following composite metal cyanide complex as a catalyst, and the terminal of the obtained oxyalkylene polymer is modified to introduce a reactive silyl group.
[0124] The polyether compound (D) can be produced, for example, by using an oxyalkylene polymer having a functional group at a molecular terminal as a raw material and bonding a reactive silyl group to the molecular terminal via an organic group such as an alkylene group. The oxyalkylene polymer used as a raw material is preferably a polymer having a hydroxyl group at the terminal obtained by ring-opening polymerization of a cyclic ether in the presence of a catalyst and an initiator.
[0125] As the above-mentioned initiator, a compound having one or more active hydrogen atoms per molecule, for example, a hydroxy compound having one or more hydroxyl groups per molecule, etc. can be used. As the initiator, for example, ethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, hexamethylene glycol, hydrogenated bisphenol A, neopentyl glycol, polybutadiene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, allyl alcohol, methallyl alcohol, glycerol, trimethylolmethane, trimethylolpropane, pentaerythritol, and hydroxy compounds such as alkylene oxide adducts thereof can be mentioned. The initiator can be one or more than two.
[0126] When the cyclic ether is subjected to ring-opening polymerization in the presence of an initiator, a polymerization catalyst may be used. Examples of the polymerization catalyst include alkali metal compounds such as potassium hydroxide and potassium methoxide, cesium compounds such as cesium hydroxide, composite metal cyanide complexes, metal porphyrin complexes, and compounds having a P=N bond.
[0127] The polyether skeleton (polyoxyalkylene chain) in the polyether compound (D) is preferably composed of oxyalkylene units formed by ring-opening polymerization of oxyalkylenes having 2 to 6 carbon atoms, more preferably composed of oxyalkylene units formed by ring-opening polymerization of at least one oxyalkylene selected from ethylene oxide, propylene oxide and butylene oxide, and particularly preferably composed of oxyalkylene units formed by ring-opening polymerization of propylene oxide. When the polyoxyalkylene chain is composed of two or more oxyalkylene units, the arrangement of the two or more oxyalkylene units may be block-like or random.
[0128] The polyether compound (D) represented by the above formula (14) can be obtained, for example, by subjecting a polymer having a polyoxyalkylene chain and a hydroxyl group to a urethanization reaction using a compound having a reactive silyl group (b) and an isocyanate group. The polyether compound (D) represented by the formula (14) can also be obtained by adding hydrosilane or mercaptosilane to an unsaturated group of an oxyalkylene polymer having an unsaturated group, for example, an allyl-terminated polyoxypropylene monool obtained by polymerizing oxyalkylene using allyl alcohol as an initiator, thereby introducing a reactive silyl group (b) at the molecular end.
[0129] The method for introducing a reactive silyl group (b) into the terminal group of the hydroxy-terminated oxyalkylene polymer obtained by ring-opening polymerization of a cyclic ether in the presence of an initiator is not particularly limited, but the following methods (a) to (c) are generally preferred, wherein the reactive silyl group is further linked to the terminal group via an organic group.
[0130] (a) A method in which an unsaturated group is introduced into the terminal of an oxyalkylene polymer having a hydroxyl group, and then a reactive silyl group (b) is bonded to the unsaturated group.
[0131] As this method, the following two methods (a-1) and (a-2) can be further exemplified.
[0132] (a-1) A method using a so-called hydrosilylation reaction in which a hydrosilane compound is reacted with the above-mentioned unsaturated group in the presence of a catalyst such as a platinum compound.
[0133] (a-2) A method of reacting a mercaptosilane compound with an unsaturated group.
[0134] Examples of the mercaptosilane compound (a-2) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltriisopropenoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyldimethylmonomethoxysilane and 3-mercaptopropylmethyldiethoxysilane.
[0135] When the unsaturated group is reacted with the thiol group, a compound such as a free radical generator used as a free radical polymerization initiator can be used. If desired, the reaction can be carried out by radiation or heat without using a free radical polymerization initiator. As free radical polymerization initiators, for example, peroxide-based, azo-based, and redox-based polymerization initiators, as well as metal compound catalysts, can be cited. Specifically, 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, benzoyl peroxide, tert-alkyl peroxide, acetyl peroxide, and diisopropyl peroxycarbonate can be cited. The reaction conditions when the unsaturated group is reacted with the thiol group using a free radical polymerization initiator vary depending on the decomposition temperature (half-life temperature) of the polymerization initiator. For example, the reaction is preferably carried out at a reaction temperature of 20 to 200°C, preferably 50 to 150°C for several hours to several tens of hours.
[0136] As a method for introducing an unsaturated group at the terminal of an oxyalkylene polymer, there can be mentioned a method of reacting an oxyalkylene polymer with a reactant having a functional group capable of linking to the terminal hydroxyl group of the oxyalkylene polymer via an ether bond, an ester bond, a urethane bond, a carbonate bond, etc. and an unsaturated group. When polymerizing a cyclic ether in the presence of an initiator, there can also be used a method of introducing an unsaturated group at least partially at the terminal of an oxyalkylene polymer by copolymerizing an unsaturated group-containing epoxy compound such as allyl glycidyl ether.
[0137] The hydrosilylation reaction is preferably carried out at a temperature of 60 to 120° C. In general, the hydrosilylation reaction proceeds sufficiently within a reaction time of several hours.
[0138] (b) A method of reacting an oxyalkylene polymer having a hydroxyl group at a terminal with an isocyanate silane compound having a reactive silyl group (b).
[0139] Examples of the isocyanate silane compound include isocyanate silane compounds such as 1-isocyanate methyl trimethoxysilane, 1-isocyanate methyl triethoxysilane, 1-isocyanate propyl trimethoxysilane, 1-isocyanate propyl triethoxysilane, 3-isocyanate propyl trimethoxysilane, 3-isocyanate propyl triethoxysilane, 1-isocyanate methyl methyl dimethoxysilane, 1-isocyanate methyl dimethyl monomethoxysilane, 1-isocyanate methyl methyl diethoxysilane, 1-isocyanate propyl methyl dimethoxysilane, 1-isocyanate propyl dimethyl monomethoxysilane, 1-isocyanate propyl methyl diethoxysilane, 3-isocyanate propyl methyl dimethoxysilane, 3-isocyanate propyl dimethyl monomethoxysilane and 3-isocyanate propyl methyl diethoxysilane. Among them, 3-isocyanatepropyltrimethoxysilane and 1-isocyanatemethylmethyldimethoxysilane are more preferred, and 3-isocyanatepropyltrimethoxysilane is particularly preferred.
[0140] The reaction of the oxyalkylene polymer and the isocyanate silane compound is preferably carried out in such a way that the molar ratio of the isocyanate group (NCO) of the isocyanate silane compound to the hydroxyl group (OH) of the oxyalkylene polymer reaches NCO / OH=0.80-1.05. Since this method has a small number of manufacturing steps, the process time can be greatly shortened, and there are also few impurities generated as by-products during the manufacturing process, so complicated operations such as purification are not required. A further preferred molar ratio of the NCO group to the OH group is NCO / OH=0.85-1.00. When the ratio of NCO is low, the reaction of the remaining OH group with the reactive silyl group occurs, and therefore, the storage stability is sometimes reduced. In this case, it is preferred to consume the excess OH group by reacting with the isocyanate silane compound or the monoisocyanate compound again, thereby adjusting to a given silylation rate.
[0141] When the hydroxyl group of the oxyalkylene polymer is reacted with the above-mentioned isocyanate silane compound, a known urethanization reaction catalyst can be used. The reaction temperature and the reaction time required until the reaction is completed vary depending on whether the urethanization reaction catalyst is used and the amount used. The reaction of the oxyalkylene polymer and the isocyanate silane compound is preferably carried out at a temperature of 20 to 200° C., preferably 50 to 150° C., for several hours.
[0142] (c) A method of reacting a polyisocyanate compound with an oxyalkylene polymer having a hydroxyl group at a molecular terminal in the presence of an excess of isocyanate groups to produce an oxyalkylene polymer having isocyanate groups at at least a part of the terminals, and further reacting a silicon compound having a functional group with the isocyanate groups.
[0143] The functional group of the silicon compound is at least one group containing active hydrogen selected from hydroxyl, carboxyl, mercapto, primary amino and secondary amino groups. Examples of the silicon compound include aminosilane compounds such as N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, and 3-aminopropylmethyldiethoxysilane; and mercaptosilane compounds such as 3-mercaptopropyltrimethoxysilane and 3-mercaptopropylmethyldimethoxysilane. When reacting the oxyalkylene polymer with the silicon compound, a known urethanization reaction catalyst can be used. The reaction temperature and the reaction time required until the reaction is completed vary depending on whether a urethanization reaction catalyst is used and the amount used. For example, the above reaction is preferably carried out at a temperature of 20 to 200° C., preferably 50 to 150° C., for several hours.
[0144] Specific examples of the polyether compound (D) include MS polymers S203, S303, and S810 manufactured by Kaneka Corporation; SILYL EST250, EST280; SAT10, SAT200, SAT220, SAT350, and SAT400 manufactured by Asahi Glass Co., Ltd.; and EXCESTAR S2410, S2420, and S3430 manufactured by Asahi Glass Co., Ltd.
[0145] In the adhesive composition, the content of the polyether compound (D) is preferably 0.001 to 20 parts by weight relative to 100 parts by weight of the base polymer. By making the content 0.001 parts by weight or more, there is a tendency that the reoperability of the adhesive layer 1 is sufficiently improved. The content of the polyether compound (D) is preferably 0.01 parts by weight or more, more preferably 0.02 parts by weight or more, further preferably 0.1 parts by weight or more, and further preferably 0.5 parts by weight or more. When the content of the polyether compound (D) is 20 parts by weight or less, the adhesive layer 1 has sufficient moisture resistance and is not easily peeled off in reliability tests, etc. The content of the polyether compound (D) is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and further preferably 3 parts by weight or less. The content of the polyether compound (D) can be 1 part by weight or less, more preferably 0.5 parts by weight or less.
[0146] <Adhesive>
[0147] Examples of the adhesive contained in the adhesive composition include rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives, cellulose adhesives, etc. As the adhesive, acrylic adhesives are preferred from the viewpoints of excellent optical transparency, appropriate adhesive properties such as wettability, cohesion, and adhesion, excellent weather resistance, heat resistance, etc.
[0148] The pressure-sensitive adhesive composition containing an acrylic pressure-sensitive adhesive contains a (meth)acrylic polymer (A) as a base polymer. The (meth)acrylic polymer (A) contains, for example, a structural unit derived from an alkyl (meth)acrylate as a main component.
[0149] <(Meth)acrylic polymer (A)>
[0150] The number of carbon atoms of the alkyl group contained in the (meth)acrylic acid alkyl ester used to form the main skeleton of the (meth)acrylic polymer (A) is not particularly limited, and is, for example, 1 to 18. The alkyl group may be linear, branched, or cyclic. Examples of the alkyl group include, for example, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isotetradecyl, undecyl, tridecyl, pentadecyl, hexadecyl, heptadecanyl, octadecyl, and the like. The (meth)acrylic acid alkyl ester may be used alone or in combination. The average number of carbon atoms of the alkyl group is preferably 3 to 9.
[0151] As monomers constituting the (meth)acrylic polymer (A), in addition to (meth)acrylic acid alkyl esters, one or more comonomers selected from aromatic ring-containing (meth)acrylic esters, amide-containing monomers, carboxyl-containing monomers, and hydroxyl-containing monomers can be cited. The comonomers can be used alone or in combination. The (meth)acrylic polymer (A) preferably has an acidic group derived from a comonomer such as a carboxyl-containing monomer. The (meth)acrylic polymer (A) having an acidic group is suitable for maintaining the reoperability of the adhesive layer 1 after preheating.
[0152] The aromatic ring-containing (meth)acrylate is a compound containing an aromatic ring structure and a (meth)acryloyl group in its structure. Examples of the aromatic ring include a benzene ring, a naphthalene ring, and a biphenyl ring. The aromatic ring-containing (meth)acrylate has an effect of adjusting the phase difference generated when stress is applied to the adhesive layer 1 by shrinking an optical film such as a polarizing film 2, and can suppress light leakage caused by shrinking the optical film.
[0153] Examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxymethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy-3-(meth)acrylate, and 1,2-dihydroxy-2-hydroxy-3-hydroxy-4-hydroxy-6 ... (Meth)acrylates having a benzene ring, such as phenoxypropyl, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, and styrene (meth)acrylate; (meth)acrylates having a naphthalene ring, such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; and (meth)acrylates containing an aromatic ring, such as biphenyl (meth)acrylate, having a biphenyl ring. Among these, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred from the viewpoint of improving the adhesive properties and durability of the adhesive layer 1.
[0154] The amide group-containing monomer is a compound containing an amide group in its structure and containing a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the amide group-containing monomer include: acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and lactam monomers containing N-vinyl groups such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. Among these, lactam monomers containing N-vinyl groups are preferred from the viewpoint of improving the durability of the conductive layer of the adhesive layer 1.
[0155] The carboxyl group-containing monomer is a compound containing a carboxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, (meth)carboxyethyl acrylate, (meth)carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among these, acrylic acid is preferred from the perspective of copolymerizability, price, and improving the adhesive properties of the adhesive layer 1.
[0156] The hydroxyl-containing monomer is a compound containing a hydroxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. As hydroxyl-containing monomers, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxydodecyl (meth)acrylate; methyl acrylate (4-hydroxymethylcyclohexyl) etc. Among these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the viewpoint of improving the durability of the adhesive layer 1, and 4-hydroxybutyl (meth)acrylate is more preferred.
[0157] The copolymerized monomer becomes a reaction point with the crosslinking agent. Carboxyl-containing monomers and hydroxyl-containing monomers are preferably used to improve the cohesion and heat resistance of the adhesive layer 1 because of their high reactivity with the intermolecular crosslinking agent. Carboxyl-containing monomers are preferred in terms of both durability and reoperability, while hydroxyl-containing monomers are preferred in terms of improving reoperability.
[0158] From the viewpoint of improving the adhesiveness of the pressure-sensitive adhesive layer 1 , the ratio of the alkyl (meth)acrylate to the total monomer components forming the (meth)acrylic polymer (A) is preferably 50% by weight or more.
[0159] When an aromatic ring-containing (meth)acrylate is used as a monomer component, from the viewpoint of improving the durability of the adhesive layer 1, the ratio of the aromatic ring-containing (meth)acrylate to the total monomer components forming the (meth)acrylic polymer (A) is preferably 3 to 25% by weight, more preferably 22% by weight or less, and further preferably 20% by weight or less. The ratio is more preferably 8% by weight or more, and further preferably 12% by weight or more. By adjusting the copolymerization ratio of the aromatic ring-containing (meth)acrylate to the above range, light leakage caused by the shrinkage of the optical film can be suppressed, and there is a tendency to improve the reoperability of the adhesive layer 1.
[0160] When a hydroxyl-containing monomer is used as a monomer component, from the viewpoint of improving the adhesive properties and durability of the adhesive layer 1, the ratio of the hydroxyl-containing monomer to the total monomer components forming the (meth) acrylic polymer (A) is preferably 0.01 to 10% by weight, more preferably 5% by weight or less, further preferably 2% by weight or less, and particularly preferably 1% by weight or less. This ratio is more preferably 0.03% by weight or more, and further preferably 0.05% by weight or more. By adjusting the copolymerization rate of the hydroxyl-containing monomer to the above range, the adhesive can be fully cross-linked in the adhesive layer 1, and the adhesive is inhibited from hardening, thereby there is a tendency to improve the durability of the adhesive layer 1.
[0161] In order to improve the adhesion and heat resistance of the adhesive layer 1, as a monomer component, in addition to the (meth)acrylate alkyl ester and the above-mentioned comonomer, other comonomers having a polymerizable functional group containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group can also be used. Other comonomers can be used alone or in combination.
[0162] Examples of other comonomers include: monomers containing anhydride groups such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, and sulfopropyl (meth)acrylate; phosphate group-containing monomers such as 2-hydroxyethylacryloyl phosphate; alkylaminoalkyl (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; methoxyethyl (meth)acrylate, and (meth)acrylate. (Meth) acrylic acid alkoxyalkyl esters such as ethoxyethyl ester; succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-dodecylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, and N-2-ethylhexylitaconimide Itaconimide monomers such as imide, N-cyclohexyl itaconimide, and N-dodecyl itaconimide; vinyl monomers such as vinyl acetate and vinyl propionate; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy (meth)acrylates such as glycidyl (meth)acrylate; glycol (meth)acrylates such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; tetrahydrofurfuryl (meth)acrylate, fluorinated (meth)acrylate, polysiloxane (meth)acrylate Acid esters, 2-methoxyethyl acrylate and other (meth)acrylate monomers; 3-acryloxypropyl triethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, 4-vinyl butyl trimethoxysilane, 4-vinyl butyl triethoxysilane, 8-vinyl octyl trimethoxysilane, 8-vinyl octyl triethoxysilane, 10-methacryloxy decyl trimethoxysilane, 10-acryloxy decyl trimethoxysilane, 10-methacryloxy decyl triethoxysilane, 10-acryloxy decyl triethoxysilane and other silane monomers containing silicon atoms.
[0163] In addition, examples of other comonomers include polyfunctional monomers having two or more unsaturated double bonds, such as tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0164] When other comonomers are used as monomer components, the ratio of other comonomers to all monomer components forming the (meth)acrylic polymer (A) is preferably 10 wt % or less, more preferably 7 wt % or less, and even more preferably 5 wt % or less.
[0165] <Method for producing (meth)acrylic polymer (A)>
[0166] The (meth)acrylic polymer (A) can be prepared by known polymerization methods such as solution polymerization, electron beam, UV radiation polymerization, bulk polymerization, emulsion polymerization and other free radical polymerization. The obtained (meth)acrylic polymer (A) may be any copolymer such as a random copolymer, a block copolymer, a graft copolymer or the like.
[0167] In solution polymerization, ethyl acetate, toluene, etc. are used as polymerization solvents. For example, a polymerization initiator is added under a stream of an inert gas such as nitrogen, and solution polymerization is usually carried out under reaction conditions of about 50 to 70° C. for about 5 to 30 hours.
[0168] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the free radical polymerization are not particularly limited and can be appropriately selected for use. The weight average molecular weight of the (meth)acrylic polymer (A) can be controlled by the amount of the polymerization initiator and chain transfer agent, the reaction conditions, etc. Therefore, the amount of the polymerization initiator and chain transfer agent can be appropriately adjusted according to their composition.
[0169] Examples of the polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N.N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate (manufactured by Wako Pure Chemical Industries, Ltd., VA-057); persulfates such as potassium persulfate and ammonium persulfate; di(2-ethylhexyl) peroxydicarbonate, di(4-hexyl) peroxydicarbonate, and the like. Peroxide initiators include peroxides such as tert-butyl cyclohexyl) ester, di-tert-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, tert-butyl peroxyisobutyrate, 1,1-di-tert-hexylperoxycyclohexane, tert-butyl hydroperoxide, and hydrogen peroxide; redox initiators such as a combination of a peroxide and a reducing agent, such as a combination of a persulfate and sodium bisulfite, a combination of a peroxide and sodium ascorbate, etc., but are not limited thereto.
[0170] The polymerization initiator may be used alone or in combination, and the total amount used is preferably about 0.005 to 1 part by weight, more preferably about 0.01 to 0.5 part by weight, based on 100 parts by weight of the monomer component.
[0171] Examples of the chain transfer agent include dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, etc. The chain transfer agent may be used alone or in combination of two or more, and the total amount used is preferably about 0.1 parts by weight or less relative to 100 parts by weight of the monomer component.
[0172] As the emulsifier used in the emulsion polymerization, for example, there can be mentioned: anionic emulsifiers such as sodium dodecyl sulfate, ammonium dodecyl sulfate, sodium dodecylbenzene sulfonate, ammonium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate; nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene fatty acid ester, polyoxyethylene-polyoxypropylene block polymer, etc. The emulsifiers can be used alone or in combination.
[0173] As reactive emulsifiers, emulsifiers into which free radical polymerizable functional groups such as acryl and allyl ether groups are introduced can be cited. Specific examples of such emulsifiers include AQUALON HS-10, HS-20, KH-10, BC-05, BC-10, BC-20 (all of which are manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), ADEKA REASOAP SE10N (manufactured by ADEKA Corporation), etc. Reactive emulsifiers enter the polymer chain after polymerization, thereby improving water resistance, and are preferred. The amount of the emulsifier used is preferably 0.3 to 5 parts by weight relative to 100 parts by weight of the total amount of the monomer components, and is more preferably 0.5 to 1 part by weight in view of polymerization stability and mechanical stability.
[0174] In radiation polymerization, the monomer components are polymerized by irradiating radiation such as electron beams and UV to produce a (meth) acrylic polymer (A). In the case of radiation polymerization by electron beams, it is not particularly necessary to contain a photopolymerization initiator in the monomer components. In the case of radiation polymerization by UV, a photopolymerization initiator may be contained in the monomer components in consideration of the advantage of shortening the polymerization time. The photopolymerization initiator may be used alone or in combination.
[0175] As the photopolymerization initiator, there is no particular limitation as long as it is an initiator that initiates photopolymerization, and commonly used photopolymerization initiators can be used. As the photopolymerization initiator, for example, benzoin ethers, acetophenones, α-ketones, photoactive oximes, benzoins, benzyls, benzophenones, ketals, thioxanthones, etc. can be used. The amount of the photopolymerization initiator used is 0.05 to 1.5 parts by weight, preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the monomer component. The photopolymerization initiator can be used alone or in combination.
[0176] The weight average molecular weight of the (meth)acrylic polymer (A) is usually 1 million to 2.5 million. Considering durability, especially heat resistance, the weight average molecular weight of the (meth)acrylic polymer (A) is preferably 1.2 million to 2 million. From the aspect of heat resistance, the weight average molecular weight is preferably 1 million or more. When the weight average molecular weight is 2.5 million or less, there is a tendency that the adhesive is not easy to harden and peel off. The weight average molecular weight (Mw) / number average molecular weight (Mn) representing the molecular weight distribution is preferably 1.8 to 10, more preferably 1.8 to 7, and further preferably 1.8 to 5. From the aspect of durability, the molecular weight distribution (Mw / Mn) is preferably 10 or less. The weight average molecular weight and molecular weight distribution (Mw / Mn) are obtained based on the values measured by GPC (gel permeation chromatography) and calculated by polystyrene conversion.
[0177] <Silane coupling agent>
[0178] In addition to compound (C) and polyether compound (D), the adhesive composition may further include a silane coupling agent (E). The silane coupling agent (E) may, for example, have a reactive functional group other than an acidic group and an anhydride group. The reactive functional group is, for example, preferably at least one selected from an epoxy group, an amino group, an isocyanate group, an isocyanurate group, a vinyl group, a styryl group, an acetoacetyl group, an ureide group, a thiourea group, a (meth)acryloyl group, and a heterocyclic group. The silane coupling agent (E) may be used alone or in combination.
[0179] Examples of the silane coupling agent (E) include epoxy-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)-1-yltrimethoxysilane; Silane coupling agents containing amino groups such as trimethoxysilane, trimethoxysilane, trieth ...
[0180] As the silane coupling agent (E), a silane coupling agent having a plurality of alkoxysilyl groups in the molecule (oligomer silane coupling agent) can also be used. Specific examples of oligomer silane coupling agents include epoxy-containing oligomer silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., trade names "X-41-1053", "X-41-1059A", "X-41-1056", "X-40-2651", etc. Oligomer silane coupling agents are not easily volatile and have a plurality of alkoxysilyl groups, so they can effectively improve the durability of the adhesive layer 1, and are therefore preferred.
[0181] When the adhesive composition contains a silane coupling agent (E), the content of the silane coupling agent (E) in the adhesive composition is preferably 0.001 to 5 parts by weight, more preferably 1 part by weight or less, and further preferably 0.6 parts by weight or less, relative to 100 parts by weight of the base polymer. The content of the silane coupling agent (E) is more preferably 0.01 parts by weight or more, further preferably 0.05 parts by weight or more, and particularly preferably 0.1 parts by weight or more, relative to 100 parts by weight of the base polymer. By appropriately adjusting the content of the silane coupling agent (E), there is a tendency to improve the durability of the adhesive layer 1.
[0182] When the adhesive composition contains a silane coupling agent (E), from the viewpoint of improving the durability of the adhesive layer 1, the weight ratio of the compound (C) to the silane coupling agent (E) (compound (C) / silane coupling agent (E)) is preferably 0.1 or more, more preferably 0.5 or more, further preferably 1 or more, and is preferably 50 or less, more preferably 15 or less, further preferably 5 or less.
[0183] <Cross-linking agent>
[0184] The adhesive composition may further include a crosslinking agent. As the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate may be used. As the organic crosslinking agent, for example, isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, etc. may be mentioned. The polyfunctional metal chelate is a chelate obtained by covalently bonding or coordinate bonding a polyvalent metal atom to an organic compound. As the polyvalent metal atom, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. may be mentioned. The covalently bonded or coordinately bonded organic compound may, for example, contain an oxygen atom, and preferably may include: an alkyl ester, an alcohol compound, a carboxylic acid compound, an ether compound, a ketone compound, etc. The crosslinking agent may be used alone or in combination.
[0185] As the crosslinking agent, an isocyanate crosslinking agent and / or a peroxide crosslinking agent is preferred, and a combination of an isocyanate crosslinking agent and a peroxide crosslinking agent is more preferred.
[0186] As the isocyanate crosslinking agent, a compound having at least two isocyanate groups (including isocyanate regenerating functional groups whose isocyanate groups are temporarily protected by a blocking agent or polymerization, etc.) can be used. For example, known aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, etc., which are generally used in urethanization reactions, can be used.
[0187] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0188] Examples of the alicyclic isocyanate include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0189] Examples of the aromatic diisocyanate include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-biphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0190] Examples of isocyanate crosslinking agents include polymers (dimers, trimers, pentamers, etc.) of the above-mentioned diisocyanates, urethane-modified products formed by reaction with polyols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, and carbodiimide-modified products.
[0191] Examples of commercially available isocyanate crosslinking agents include "Millionate MT", "Millionate MTL", "Millionate MR-200", "Millionate MR-400", "Coronate L", "Coronate HL", and "Coronate HX" manufactured by Tosoh Corporation, and "Takenate D-110N", "Takenate D-120N", "Takenate D-140N", "Takenate D-160N", "Takenate D-165N", "Takenate D-170HN", "Takenate D-178N", "Takenate 500", and "Takenate 600" manufactured by Mitsui Chemicals, Inc.
[0192] As the isocyanate crosslinking agent, aromatic polyisocyanates and aromatic polyisocyanate compounds as modified products thereof, aliphatic polyisocyanates and aliphatic polyisocyanate compounds as modified products thereof are preferred. Aromatic polyisocyanate compounds have a good balance between crosslinking speed and pot life, and are therefore preferably used. As aromatic polyisocyanate compounds, toluene diisocyanate and modified products thereof are particularly preferred.
[0193] As the peroxide, any peroxide can be used as long as it generates free radical active species by heating or light irradiation and crosslinks the base polymer (e.g., (meth)acrylic polymer (A)) of the adhesive composition. However, in consideration of operability and stability, it is preferred to use a peroxide with a 1-minute half-life temperature of 80°C to 160°C, and more preferably a peroxide with a 1-minute half-life temperature of 90°C to 140°C.
[0194] Examples of the peroxide include di(2-ethylhexyl) peroxydicarbonate (1-minute half-life temperature: 90.6° C.), di(4-tert-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butyl peroxydicarbonate (1-minute half-life temperature: 92.4° C.), tert-butyl peroxyneodecanoate (1-minute half-life temperature: 103.5° C.), tert-hexyl peroxypivalate (1-minute half-life temperature: 109.1° C.), tert-butyl peroxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide (1 Half-life temperature (1 minute): 116.4°C), dioctanoyl peroxide (1 minute half-life temperature: 117.4°C), 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate (1 minute half-life temperature: 124.3°C), di(4-methylbenzoyl) peroxide (1 minute half-life temperature: 128.2°C), dibenzoyl peroxide (1 minute half-life temperature: 130.0°C), tert-butyl peroxyisobutyrate (1 minute half-life temperature: 136.1°C), 1,1-di(tert-hexylperoxide)cyclohexane (1 minute half-life temperature: 149.2°C). Among them, since the cross-linking reaction efficiency is particularly excellent, di(4-tert-butylcyclohexyl) peroxydicarbonate (1 minute half-life temperature: 92.1°C), dilauroyl peroxide (1 minute half-life temperature: 116.4°C), dibenzoyl peroxide (1 minute half-life temperature: 130.0°C), etc. can be cited.
[0195] The half-life of peroxide is an index representing the decomposition rate of peroxide, refers to the time until the residual amount of peroxide becomes half. About obtaining the decomposition temperature of half-life at any time, the half-life time under any temperature, in the manufacturer's catalogue etc., record to some extent, for example, be recorded in " Organic Peroxide Catalogue the 9th edition (May, 2003) " etc. of Japan Oil and Fats Co., Ltd.
[0196] When a crosslinking agent is added to the adhesive composition, the amount of the crosslinking agent is preferably 0.01 to 3 parts by weight, more preferably 0.02 to 2 parts by weight, and further preferably 0.03 to 1 part by weight relative to 100 parts by weight of the base polymer. When the amount of the crosslinking agent is 0.01 parts by weight or more, the adhesive layer 1 is fully crosslinked, and there is a tendency to improve durability and adhesive properties. On the other hand, when the amount of the crosslinking agent is 3 parts by weight or less, there is a tendency to suppress the adhesive layer 1 from becoming hard and reducing durability.
[0197] When an isocyanate crosslinking agent is added to the adhesive composition, the amount of the isocyanate crosslinking agent is preferably 0.01 to 2 parts by weight, more preferably 0.02 to 2 parts by weight, and even more preferably 0.05 to 1.5 parts by weight relative to 100 parts by weight of the base polymer. When the amount of the isocyanate crosslinking agent is within the above range, the cohesive force of the adhesive layer 1 tends to be improved, and peeling in a durability test tends to be suppressed.
[0198] When a peroxide is added to the adhesive composition, the amount of the peroxide added is preferably 0.01 to 2 parts by weight, more preferably 0.04 to 1.5 parts by weight, and even more preferably 0.05 to 1 part by weight relative to 100 parts by weight of the base polymer. When the amount of the peroxide added is within the above range, the processability, crosslinking stability, etc. of the adhesive layer 1 can be easily adjusted.
[0199] <Other ingredients>
[0200] The adhesive composition may further include an ionic compound. As the ionic compound, there is no particular limitation, and those used in the art can be preferably used. As the ionic compound, for example, the ionic compounds described in Japanese Patent Publication No. 2015-4861 can be cited, among which (perfluoroalkylsulfonyl)imide lithium salts are preferred, and bistrifluoromethylsulfonyl imide lithium is more preferred. The amount of the ionic compound is not particularly limited, and can be set to a range that does not impair the effect of the present invention, for example, relative to 100 parts by weight of the base polymer, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, further preferably 3 parts by weight or less, and particularly preferably 1 part by weight or less.
[0201] The adhesive composition may contain other known additives, such as colorants, pigments, powders, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, granular, foil-like objects, etc., according to the purpose of use. In addition, within the controllable range, redox-type reducing agents may also be used. These additives are preferably used in an amount of less than 5 parts by weight, more preferably less than 3 parts by weight, and further preferably less than 1 part by weight relative to 100 parts by weight of the base polymer.
[0202] <Method for producing adhesive layer>
[0203] When forming the adhesive layer 1 from the adhesive composition, it is preferred to adjust the total amount of the crosslinking agent added to the adhesive composition while fully considering the influence of the crosslinking treatment temperature and the crosslinking treatment time.
[0204] The crosslinking treatment temperature and the crosslinking treatment time can be appropriately adjusted according to the crosslinking agent used. The crosslinking treatment temperature is preferably below 170°C. The crosslinking treatment can be carried out at the temperature during the drying process of the adhesive layer 1, or a crosslinking treatment process can be set separately after the drying process. The crosslinking treatment time can be set in consideration of productivity and operability, but is usually about 0.2 to 20 minutes, preferably about 0.5 to 10 minutes.
[0205] The method for forming the adhesive layer 1 is not particularly limited. It can be a method of coating the adhesive composition on various substrates, drying it in a dryer such as a hot oven to evaporate the solvent, and performing cross-linking treatment as needed to form the adhesive layer 1, and then transferring the adhesive layer 1 to the polarizing film 2; or it can be a method of directly coating the adhesive composition on the polarizing film 2 to form the adhesive layer 1.
[0206] The substrate is not particularly limited, and examples thereof include various substrates such as a release film and a transparent resin film substrate.
[0207] Various methods can be used to apply the adhesive composition to the substrate or polarizing film 2. Specific examples include spray coating, roll coating, lick coating, gravure coating, reverse coating, roller brushing, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, extrusion coating using a die coater, and the like.
[0208] The drying conditions (temperature, time) are not particularly limited and can be appropriately set according to the composition and concentration of the adhesive composition, for example, drying at about 80 to 170° C., preferably 90 to 200° C., for 1 to 60 minutes, preferably 2 to 30 minutes. A crosslinking treatment may be performed after drying as needed, and the conditions are as described above.
[0209] The thickness of the adhesive layer 1 (after drying) is, for example, preferably 5 to 100 μm, more preferably 7 to 70 μm, and further preferably 10 to 50 μm. When the thickness of the adhesive layer 1 is 5 μm or more, the adhesion to the adherend is improved, and there is a tendency to have sufficient durability under humidified conditions. On the other hand, when the thickness of the adhesive layer is 100 μm or less, the adhesive composition when forming the adhesive layer 1 can be fully dried, and the remaining bubbles and the occurrence of uneven thickness of the adhesive layer 1 can be suppressed, and there is a tendency that problems in appearance are not easy to occur.
[0210] As the constituent material of the release film, for example, resin films such as polyethylene, polypropylene, polyethylene terephthalate, polyester film, porous materials such as paper, cloth, nonwoven fabrics, nets, foam sheets, metal foils, and laminates thereof can be cited. As the release film, from the aspect of excellent surface smoothness, it is preferred to use a resin film. As the resin film, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, etc. can be cited.
[0211] The thickness of the release film is usually 5 to 200 μm, preferably about 5 to 100 μm. The release film may be subjected to release treatment and antifouling treatment using release agents such as silicone, fluorine, long-chain alkyl, fatty acid amide, silica powder, etc., or subjected to antistatic treatment such as coating, mixing, and vapor deposition. In particular, the release property relative to the adhesive layer 1 can be further improved by appropriately subjecting the surface of the release film to a release treatment such as silicone treatment, long-chain alkyl treatment, and fluorine treatment.
[0212] As the transparent resin film substrate, there is no particular limitation, and various resin films with transparency can be used. The resin film can be formed by a single layer of film. For example, as its material, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyacrylate resins, polyphenylene sulfide resins, etc. are mentioned. Among these, polyester resins, polyimide resins and polyethersulfone resins are particularly preferred. The thickness of the film substrate is preferably 15 to 200 μm.
[0213] [Polarizing film]
[0214] The polarizing film 2 is a laminated body including a polarizer and a transparent protective film. The transparent protective film is disposed, for example, in contact with the principal surface (surface having the largest area) of the layered polarizer. The polarizer may be disposed between two transparent protective films.
[0215] The polarizer is not particularly limited, and various polarizers can be used. Examples of the polarizer include films obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and then uniaxially stretching them; polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. Among these, a polarizer formed of a polyvinyl alcohol film and a dichroic substance such as iodine is preferred, and an iodine-based polarizer containing iodine and / or iodide ions is more preferred. The thickness of the polarizer is not particularly limited, and is usually about 5 to 80 μm.
[0216] In the case of polyvinyl alcohol films, polyvinyl alcohol undergoes polyene conversion by dehydration reaction under high temperature conditions, and thus the optical properties of the film may be degraded. When the polarizing film 2 has a high moisture content, polyene conversion tends to occur significantly. Therefore, when the polyvinyl alcohol film is used as a polarizer, preheating to reduce the moisture content of the polarizing film 2 is particularly important.
[0217] The polarizer formed by dyeing the polyvinyl alcohol film with iodine and uniaxially stretching can be made, for example, by immersing the polyvinyl alcohol in an aqueous solution of iodine to dye it and stretching it to 3 to 7 times its original length. As needed, the polyvinyl alcohol can be immersed in an aqueous solution of potassium iodide containing boric acid, zinc sulfate, zinc chloride, etc. Further, as needed, the polyvinyl alcohol film can be immersed in water for washing before dyeing. By washing the polyvinyl alcohol film, in addition to washing away the dirt and anti-blocking agent on the surface of the polyvinyl alcohol film, it also has the effect of swelling the polyvinyl alcohol film and suppressing the occurrence of uneven dyeing. The stretching of the polyvinyl alcohol film can be carried out after dyeing with iodine, it can also be carried out while dyeing, and it can also be carried out before dyeing with iodine. Stretching can be carried out in an aqueous solution of boric acid, potassium iodide, etc., or in a water bath.
[0218] As the polarizer, a thin polarizer with a thickness of 10 μm or less may be used. From the perspective of thinning, the thickness of the polarizer is preferably 1 to 7 μm. Such a thin polarizer has less uneven thickness, excellent visual recognition, and less dimensional change, so it has excellent durability and can further achieve thinning of the polarizing film 2, which is preferred from these aspects.
[0219] As representative thin polarizers, thin polarizing films described in Japanese Patent Publication No. 51-069644, Japanese Patent Publication No. 2000-338329, International Publication No. 2010 / 100917, Japanese Patent No. 4751481, and Japanese Patent Publication No. 2012-073563 can be cited. These thin polarizing films can be obtained by a production method including a step of stretching a polyvinyl alcohol resin (hereinafter also referred to as PVA) layer and a stretching resin substrate in a laminated state, and a step of dyeing. According to this production method, the PVA resin layer is supported by the stretching resin substrate, so even if the PVA resin layer is thin, it is possible to suppress undesirable conditions such as breakage caused by stretching.
[0220] In the method including the step of stretching in the state of a stack and the step of dyeing, from the aspect of being able to stretch at a high ratio to improve the polarization performance, the method including the step of stretching in an aqueous boric acid solution described in International Publication No. 2010 / 100917, Japanese Patent No. 4751481, and Japanese Patent Gazette No. 2012-073563 is preferred, and the method including the step of auxiliary stretching in a gas atmosphere before stretching in an aqueous boric acid solution described in Japanese Patent No. 4751481 and Japanese Patent Gazette No. 2012-073563 is particularly preferred.
[0221] As the material for forming the transparent protective film disposed on one or both sides of the polarizer, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the transparent protective film can be a thermosetting resin or an ultraviolet curing resin such as (meth)acrylic acid, carbamate, acrylic carbamate, epoxy, silicone, etc. In the case where the polarizing film 2 has two transparent protective films, the materials of the two transparent protective films can be the same or different. For example, a transparent protective film composed of a thermoplastic resin can be bonded to one main surface of the polarizer by an adhesive, and a transparent protective film composed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The transparent protective film can contain one or more arbitrary additives. As additives, for example, ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, etc. can be cited. The content of thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. When the content of thermoplastic resin in the transparent protective film is 50% by weight or more, there is a tendency to fully display the high transparency originally possessed by the thermoplastic resin.
[0222] The thickness of the transparent protective film can be appropriately determined, and is generally about 10 to 200 μm in view of strength, workability such as handling properties, and thin film properties.
[0223] The moisture permeability of at least one transparent protective film included in the polarizing film 2 is preferably 300 g / m 2 24h or more, more preferably 500g / m 2 24h or more, more preferably 800g / m 2 · 24h or more. When the moisture permeability of the transparent protective film is high, the moisture content of the polarizing film 2 can be easily reduced by preheating. On the other hand, when the moisture permeability of the transparent protective film is too high, the humidification durability of the polarizing film 2 may be reduced. Therefore, the moisture permeability of the transparent protective film is preferably 1600g / m 2 24h or less, more preferably 1300g / m 2Less than 24 hours. It should be noted that the moisture permeability is a value measured based on the moisture permeability test (cup method) of JIS Z0208, which is the value of the moisture permeability measured from an area of 1m2 under the conditions of 40°C and 90% relative humidity within 24 hours. 2 The weight of water vapor transmitted by a sample.
[0224] The polarizer and the transparent protective film are usually bonded together by a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Examples of adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizing film adhesives show appropriate adhesion to various transparent protective films. The adhesive may also contain a metal compound filler.
[0225] In the polarizing film 2, a retardation film or the like may be formed on the polarizer instead of the transparent protective film. Another transparent protective film or a retardation film or the like may be further provided on the transparent protective film.
[0226] The transparent protective film may be provided with a hard coat layer on the surface opposite to the surface to which the polarizer is bonded, or may be subjected to treatment for the purpose of anti-reflection, anti-sticking, diffusion, anti-glare, etc.
[0227] [Other components]
[0228] The polarizing film 10 with an adhesive layer may further include other optical films in addition to the polarizing film 2. As other optical films, for example, films used for liquid crystal display devices such as reflective plates, reflective transmission plates, phase difference films, viewing angle compensation films, and brightness enhancement films can be cited. Phase difference films include, for example, 1 / 2 wave plates, 1 / 4 wave plates, etc. The polarizing film 10 with an adhesive layer may include one or more other optical films among these.
[0229] The polarizing film 10 with an adhesive layer may further include an adhesion-enhancing layer, which is located between the polarizing film 2 and the adhesive layer 1. The material forming the adhesion-enhancing layer is not particularly limited, and examples thereof include: various polymers, metal oxide sols, silica sols, etc. Among these, polymers are particularly preferably used. The polymers may be used in any form of solvent-soluble, water-dispersible, or water-soluble.
[0230] Examples of the polymers include polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, polyvinyl pyrrolidone, and polystyrene resins.
[0231] When the adhesive layer 1 of the polarizing film 10 with an adhesive layer is exposed, the adhesive layer 1 can be protected by a release film (spacer) until it is used. As the release film, those described above can be cited. When the adhesive layer 1 is produced, when a release film is used as a substrate, the adhesive layer 1 on the release film is bonded to the polarizing film 2, and the release film can be used as a release film of the adhesive layer 1 of the polarizing film 10 with an adhesive layer, which can simplify the process.
[0232] [Properties of Adhesive Layer]
[0233] Next, the reasons why the pressure-sensitive adhesive layer 1 of the pressure-sensitive adhesive layer-attached polarizing film 10 can maintain re-handling properties after preheating and has durability in a high-temperature environment even when attached to a conductive layer will be described together with the mechanism considered.
[0234] After the adhesive layer 1 is formed from the adhesive composition, the acid anhydride groups of the compound (C) in the adhesive layer 1 are hydrolyzed by moisture in the air, thereby changing to acidic groups. On the other hand, on the surface of the conductive layer containing a metal oxide such as ITO, there are not only hydroxyl groups but also metal cations generated by the detachment of hydroxyl groups in the form of hydroxide ions. Figure 2 As shown, when the polarizing film 10 with an adhesive layer is attached to the conductive layer 3 via the adhesive layer 1, the acidic group of the compound (C) is deprotonated by a neutralization reaction with the hydroxide ions present near the surface of the conductive layer 3. The anions thus generated form ionic bonds with the metal cations on the surface of the conductive layer 3. That is, an acid-base reaction occurs between the acidic group of the compound (C) and the conductive layer 3. It is inferred that the compound (C) is segregated on the surface of the conductive layer 3, and the first layer 11 containing the compound (C) is formed in the adhesive layer 1.
[0235] After the first layer 11 is formed, the polyether compound (D) tends to segregate on the surface of the first layer 11. Therefore, in the adhesive layer 1, the second layer 12 containing the polyether compound (D) is formed on the first layer 11. It should be noted that, when the adhesive layer 1 does not contain the compound (C), the polyether compound (D) is basically not segregated on the surface of the conductive layer 3. Therefore, the first layer 11 can be regarded as a surface modification layer that modifies the surface of the conductive layer 3 so that the polyether compound (D) is easily segregated.
[0236] In this way, it can be inferred that the first layer 11 and the second layer 12 are formed in the adhesive layer 1 by attaching the polarizing film 10 with an adhesive layer to the conductive layer 3 using the adhesive layer 1. By forming the first layer 11 and the second layer 12, for example, the third layer 13 mainly containing an adhesive is further formed in the adhesive layer 1. The first layer 11, the second layer 12, and the third layer 13 are arranged in this order in the stacking direction.
[0237] Before preheating, the cohesive force of the first layer 11 and the second layer 12 is smaller than that of the third layer 13. Therefore, before preheating, the pressure-sensitive adhesive layer-attached polarizing film 10 can be easily peeled from the conductive layer 3 by cohesive failure of the first layer 11 or the second layer 12.
[0238] For example, when preheating is performed at a temperature of about 70°C to 95°C, there is a tendency for the cohesive force of the first layer 11 to increase significantly due to the reaction of the compound (C) or the like. The increase in the cohesive force of the first layer 11 is particularly significant when the compound (C) contains a hydrolyzable group (h1). On the other hand, the cohesive force of the second layer 12 is not easily increased compared to the first layer 11. Therefore, after preheating, the polarizing film 10 with an adhesive layer can be easily peeled off from the conductive layer 3 by cohesive destruction at the second layer 12 or at the interface between the first layer 11 and the second layer 12. That is, the second layer 12 functions as a layer that ensures the reoperability of the adhesive layer 1 after preheating.
[0239] From the outside, when the adhesive layer 1 is arranged in an environment with a temperature higher than 95°C, there is a tendency that the cohesive force of the second layer 12 is greatly increased due to the reaction of the polyether compound (D) and the like. The increase in the cohesive force of the second layer 12 is particularly significant when the polyether compound (D) contains a hydrolyzable group (h2). As a result, there is a tendency that the adhesive force between the adhesive layer 1 and the conductive layer 3 is greatly increased, and the durability of the adhesive layer 1 is improved.
[0240] From another aspect, the present invention provides an adhesive layer 1, which is formed from an adhesive composition.
[0241] The adhesive composition comprises a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D),
[0242] Adhesion force P obtained by test 1 85 The adhesive force P obtained by test 2 is 10.0 N / 25 mm or less. 105 Greater than 10.0N / 25mm.
[0243] (Embodiment of Image Display Panel)
[0244] like Figure 3As shown, the image display panel 100 of the present embodiment includes a polarizing film 10 with an adhesive layer, a conductive layer 3, and a transparent substrate 4. The conductive layer 3 and the transparent substrate 4 are, for example, components constituting the liquid crystal cell 20. That is, the image display panel 100 is a liquid crystal display panel including the polarizing film 10 with an adhesive layer and the liquid crystal cell 20. However, the image display panel 100 may also include an organic EL cell instead of the liquid crystal cell 20. In the image display panel 100, the polarizing film 10 with an adhesive layer is, for example, arranged closer to the visible side than the liquid crystal cell 20.
[0245] The polarizing film 10 with an adhesive layer, the conductive layer 3, and the transparent substrate 4 are arranged in sequence in the stacking direction, for example, and the adhesive layer 1 of the polarizing film 10 with an adhesive layer is directly in contact with the conductive layer 3. In other words, the polarizing film 10 with an adhesive layer is attached to the conductive layer 3 via the adhesive layer 1. The conductive layer 3 is, for example, directly in contact with the transparent substrate 4. Other layers such as a primer layer and an oligomer prevention layer may be arranged between the conductive layer 3 and the transparent substrate 4 as needed.
[0246] [Adhesive layer]
[0247] As described above, when the polarizing film 10 with an adhesive layer is attached to the conductive layer 3 via the adhesive layer 1, the first layer 11, the second layer 12, and the third layer 13 are formed in the adhesive layer 1. The conductive layer 3, the first layer 11, the second layer 12, and the third layer 13 are arranged in this order in the stacking direction, and the third layer 13 is located between the second layer 12 and the polarizing film 2.
[0248] The first layer 11 includes, for example, a compound (C) or a reactant (R1) thereof. When the compound (C) includes a hydrolyzable group (h1), the reactant (R1) is, for example, a hydrolysis condensate of a plurality of compounds (C), or a reactant of the compound (C) and a hydroxyl group on the surface of the conductive layer 3. The first layer 11 may include the compound (C) or a reactant (R1) thereof as a main component.
[0249] The second layer 12 contains, for example, a polyether compound (D) or a reactant thereof (R2). When the polyether compound (D) contains a hydrolyzable group (h2), the reactant (R2) is, for example, a hydrolysis condensate of a plurality of polyether compounds (D). The second layer 12 may contain a polyether compound (D) or a reactant thereof (R2) as a main component.
[0250] The third layer 13 contains a base polymer such as a (meth) acrylic polymer (A) or a reactant (R3) thereof. When the adhesive composition forming the adhesive layer 1 contains a crosslinking agent, the reactant (R3) is, for example, a crosslinked product of the (meth) acrylic polymer (A). The third layer 13 may contain the (meth) acrylic polymer (A) or a reactant (R3) thereof as a main component.
[0251] It should be noted that the adhesive layer 1 having the first layer 11, the second layer 12 and the third layer 13 can be confirmed by methods such as time-of-flight secondary ion mass spectrometry (TOF-SIMS: Time-of-Flight Secondary Ion Mass Spectrometry). For example, an adhesive composition for forming the adhesive layer 1 is prepared. The adhesive composition is applied to the conductive layer 3 to prepare a coating film having a thickness of about 1 μm after drying. For the film obtained by drying the coating film, an analysis based on TOF-SIMS is performed from its surface to the thickness direction of the film. Thus, it can be confirmed that the adhesive layer 1 has the first layer 11, the second layer 12 and the third layer 13.
[0252] [Conductive layer]
[0253] The conductive layer 3 is not particularly limited as long as it contains a metal oxide. As the metal oxide, for example, an oxide containing at least one metal selected from indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium and tungsten can be cited. The conductive layer 3 not only contains metal oxides, but also can contain metals shown in the above group as needed. For example, the material of the conductive layer 3 is preferably indium tin oxide, tin oxide containing antimony, etc. Indium tin oxide refers to indium oxide containing tin oxide, which is called indium-tin composite oxide, ITO. The conductive layer 3 preferably contains ITO, and more preferably is substantially formed by ITO.
[0254] The content of indium oxide in ITO contained in the conductive layer 3 is preferably 80 to 99% by weight. The content of tin oxide in ITO is preferably 1 to 20% by weight. ITO may be crystalline or amorphous.
[0255] The thickness of the conductive layer 3 is not particularly limited, but is preferably 10 nm or more, more preferably 15 to 40 nm, and even more preferably 20 to 30 nm.
[0256] The method for forming the conductive layer 3 is not particularly limited, and a conventionally known method can be used. Specifically, the conductive layer 3 can be formed by vacuum deposition, sputtering, ion plating, etc. These methods can be appropriately selected according to the desired film thickness of the conductive layer 3.
[0257] [Transparent substrate]
[0258] The transparent substrate 4 may be made of any material as long as it is transparent. Examples of the transparent substrate 4 include glass and a transparent resin film substrate. Examples of the transparent resin film substrate include those mentioned above.
[0259] [Liquid crystal unit]
[0260] The liquid crystal cell 20 includes, for example, a liquid crystal layer 5 and a transparent substrate 6 in addition to the conductive layer 3 and the transparent substrate 4. In the liquid crystal cell 20, the conductive layer 3, the transparent substrate 4, the liquid crystal layer 5 and the transparent substrate 6 are arranged in this order in the stacking direction.
[0261] The liquid crystal layer 5 is not particularly limited, and any type of liquid crystal layer, such as TN type, STN type, π type, VA type, IPS type, etc., can be used. The transparent substrate 6 is not particularly limited in material as long as it is a transparent substrate. Examples of the transparent substrate 6 include glass and a transparent resin film substrate. Examples of the transparent resin film substrate include those mentioned above.
[0262] [Other components]
[0263] The image display panel 100 may include optical films such as a phase difference film, a viewing angle compensation film, and a brightness enhancement film in addition to the polarizing film 10 with a pressure-sensitive adhesive layer and the liquid crystal cell 20 .
[0264] [Method for manufacturing image display panel]
[0265] The method for manufacturing the image display panel 100 is not particularly limited, and includes, for example, first heating the pressure-sensitive adhesive layer 1 at 70° C. to 95° C. in a state where the pressure-sensitive adhesive layer-attached polarizing film 10 is bonded to the conductive layer 3 .
[0266] The first heat treatment corresponds to preheating for reducing the moisture content of the polarizing film 2. The temperature of the first heat treatment is preferably 80° C. to 95° C. The time of the first heat treatment is not particularly limited, and is, for example, 1 to 5 hours, and preferably 3 to 5 hours.
[0267] The moisture content of the polarizing film 2 after the first heat treatment is not particularly limited, and is, for example, 7 g / m 2 The following is the result of the following analysis: The water content of the polarizing film 2 can be measured by the method described in Patent Document 1.
[0268] The manufacturing method of the image display panel 100 may further include, after the first heat treatment, performing a second heat treatment on the adhesive layer 1 at a temperature higher than 95° C. The second heat treatment tends to significantly increase the adhesive force of the adhesive layer 1 and improve the durability of the adhesive layer 1. The temperature of the second heat treatment may be 100° C. to 150° C. The time of the second heat treatment is not particularly limited, and is, for example, 1 hour to 1000 hours, and preferably 24 hours or more.
[0269] (Modification of Image Display Panel)
[0270] The image display panel 100 may include two polarizing films 10 with adhesive layers. Figure 4As shown in FIG. 1 , the image display panel 110 of this modified example includes two polarizing films 10a and 10b with adhesive layers. The structure of the image display panel 110 is the same as that of the image display panel 100 except for the polarizing film 10b with adhesive layers. Therefore, the same reference numerals are used for the common elements in the image display panel 100 and the image display panel 110 of the modified example, and their description is sometimes omitted.
[0271] The adhesive layer-attached polarizing film 10b is attached to the transparent substrate 6 of the liquid crystal cell 20 via the adhesive layer 1b. In the image display panel 110, the liquid crystal cell 20 is located between the adhesive layer-attached polarizing films 10a and 10b and is located closer to the visible side than the adhesive layer-attached polarizing film 10b.
[0272] The pressure-sensitive adhesive layer 1b and the polarizing film 2b of the pressure-sensitive adhesive layer-attached polarizing film 10b may be the same as or different from the pressure-sensitive adhesive layer 1a and the polarizing film 2a of the pressure-sensitive adhesive layer-attached polarizing film 10a. The pressure-sensitive adhesive layer 1b and the polarizing film 2b may be those conventionally used in the art.
[0273] (Embodiment of Image Display Device)
[0274] The image display device of this embodiment includes, for example, an image display panel 100 and a lighting system. In the image display device, an image display panel 110 may be used instead of the image display panel 100. In the image display device, the image display panel 100 is, for example, arranged closer to the visible side than the lighting system. The lighting system includes, for example, a backlight or a reflector, and irradiates light to the image display panel 100.
[0275] Examples of image display devices include liquid crystal display devices, organic electroluminescent (EL) displays, plasma displays (PD), field emission displays (FED), etc. These image display devices can be used for home appliances, vehicles, public information displays (PID), etc., and are particularly preferably used for vehicles.
[0276] Example
[0277] The present invention is described in more detail below by way of examples, but the present invention is not limited to the examples shown below. It should be noted that, below, unless otherwise specified, "%" means "weight %", "part" means "weight part", and "thickness" means "physical film thickness". Unless otherwise specified, the indoor temperature and humidity are 23°C and 65%RH.
[0278] (Acrylic polymer (A1))
[0279] A monomer mixture containing 100 parts by weight of butyl acrylate (BA), 0.075 parts by weight of 4-hydroxybutyl acrylate (HBA), and 5 parts by weight of acrylic acid (AA) was added to a 4-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts by weight of the monomer mixture, and nitrogen was introduced while slowly stirring to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 6 hours. Thus, a solution of an acrylic polymer (A1) with a weight average molecular weight of 2.4 million and Mw / Mn=4.5 was prepared.
[0280] (Acrylic polymer (A2))
[0281] Except having changed the monomer used as shown in Table 1, the solution of the acrylic polymer (A2) was prepared by the same method as that of the acrylic polymer (A1).
[0282] (Acrylic oligomer (B1))
[0283] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 85 parts by weight of butyl acrylate (BA), 15 parts by weight of acrylic acid (AA), 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, 100 parts by weight of toluene, and 3.5 parts by weight of α-thioglycerol were added, and nitrogen was fully introduced while slowly stirring to replace the nitrogen. The liquid temperature in the flask was maintained at about 60°C, and a polymerization reaction was performed for 4 hours to prepare a solution of an acrylic oligomer (B1). The weight average molecular weight of the acrylic oligomer (B1) was 6700.
[0284] (Acrylic oligomer (B2))
[0285] Except having changed the monomer used as shown in Table 1, the acrylic oligomer (B2) was prepared by the same method as that of the acrylic oligomer (B1).
[0286] [Table 1]
[0287]
[0288] The abbreviations in Table 1 are as follows.
[0289] BA: n-butyl acrylate
[0290] HBA: 4-Hydroxybutyl Acrylate
[0291] AA: Acrylic acid
[0292] PEA: Phenoxyethyl acrylate
[0293] NVP: N-vinyl-2-pyrrolidone
[0294] MEA: 2-Methoxyethyl acrylate
[0295] (Compound (C1))
[0296] Compound (C1) was prepared according to the method described in Example 1 of Japanese Patent Application Publication No. 2013-129809. Compound (C1) is an organopolysiloxane compound comprising the above-mentioned siloxane units (U1) and (U2). In the siloxane unit (U1), X is a propyl succinic anhydride group, R 4 In the siloxane unit (U2), two R 4 All of them are methoxy groups. The content of the siloxane unit (U1) in the compound (C1) is 27 mol%. The content of the siloxane unit (U2) in the compound (C1) is 73 mol%. The weight average molecular weight of the compound (C1) is about 1,000.
[0297] (Polarizing Film)
[0298] [TAC film with HC]
[0299] First, a resin solution (DIC, trade name: UNIDIC 17-806, solid content concentration: 80%) obtained by dissolving an ultraviolet curable resin monomer or oligomer with urethane acrylate as the main component in butyl acetate was prepared. Next, 5 parts of a photopolymerization initiator (BASF, trade name: IRGACURE907) and 0.1 parts of a leveling agent (DIC, trade name: GRANDIC PC4100) were added to the resin solution relative to 100 parts of the solid content of the resin solution. Next, cyclopentanone and propylene glycol monomethyl ether were added to the solution at a ratio of 45:55, and the solid content concentration of the obtained solution was made to reach 36%, thereby preparing a material for forming a hard coating layer. Next, the material was coated on a TAC film (TJ40UL manufactured by Fujifilm Corporation, raw material: triacetyl cellulose polymer, thickness: 40μm), and the thickness of the hard coating layer after curing was made to reach 7μm, thereby forming a coating film. Next, the coating film was dried at 90°C for 1 minute and further irradiated with a high pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 The coating film was cured by ultraviolet light to form a hard coating layer (HC). Thus, a TAC film with HC was produced.
[0300] [Acrylic film]
[0301] In a 30L kettle reactor equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet pipe, 8000g of methyl methacrylate (MMA), 2000g of methyl 2-(hydroxymethyl)acrylate (MHMA), 10000g of 4-methyl-2-pentanone (methyl isobutyl ketone, MIBK), and 5g of n-dodecyl mercaptan were added, and the temperature was raised to 105°C while nitrogen was passed therethrough. After the start of reflux, 5.0g of tert-butyl peroxyisopropyl carbonate (Kayakarubon BIC-7, manufactured by Kayaku Akzo Co., Ltd.) was added as a polymerization initiator, and a solution prepared by 10.0g of tert-butyl peroxyisopropyl carbonate and 230g of MIBK was added dropwise over 4 hours, and solution polymerization was carried out at about 105 to 120°C under reflux, and aging was further carried out over 4 hours.
[0302] 30 g of a mixture of stearyl phosphate / distearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry) was added to the obtained polymer solution, and a cyclocondensation reaction was carried out at about 90 to 120° C. for 5 hours under reflux. Next, the obtained polymer solution was introduced into a vented twin-screw extruder (φ=29.75 mm, L / D=30) with a barrel temperature of 260° C., a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), 1 rear vent hole, and 4 front vent holes at a processing rate of 2.0 kg / h according to the resin amount. Further cyclocondensation reaction and devolatilization were carried out in the extruder. Thus, transparent particles of a lactone ring-containing polymer were obtained.
[0303] The obtained lactone ring-containing polymer was subjected to dynamic TG measurement, and a mass loss of 0.17 mass % was detected. The lactone ring-containing polymer had a weight average molecular weight of 133,000, a melt flow rate of 6.5 g / 10 min, and a glass transition temperature of 131°C.
[0304] The obtained pellets were kneaded and extruded with acrylonitrile-styrene (AS) resin (ToyoAS AS20, manufactured by Toyo Styrene Co., Ltd.) at a mass ratio of 90 / 10 using a single screw extruder (screw 30 mmφ) to obtain transparent pellets. The obtained pellets had a glass transition temperature of 127°C.
[0305] The pellets were melt-extruded from a 400 mm wide coat hanger T die using a 50 mm φ single screw extruder to produce a 120 μm thick film. The film was stretched to 2.0 times in the longitudinal direction and 2.0 times in the transverse direction at a temperature of 150° C. using a biaxial stretching device to obtain a 30 μm thick stretched film (acrylic film). The optical properties of the stretched film were measured, and the results showed that the total light transmittance was 93%, the in-plane phase difference Δnd was 0.8 nm, and the thickness direction phase difference Rth was 1.5 nm.
[0306] Next, a polarizing film was produced by the following method. First, a polyvinyl alcohol film with a thickness of 45 μm was dyed in a 0.3% iodine solution (temperature 30°C) between multiple rollers with different speed ratios for 1 minute, and stretched to a stretch ratio of 3 times. Next, the obtained stretched film was immersed in an aqueous solution (temperature 60°C) containing 4% boric acid and 10% potassium iodide for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, the stretched film was immersed in an aqueous solution (temperature 30°C) containing 1.5% potassium iodide for 10 seconds and washed. Next, a polarizer with a thickness of 18 μm was obtained by drying the stretched film at 50°C for 4 minutes. The above-mentioned TAC film with HC that was saponified was bonded to one main surface of the obtained polarizer using a polyvinyl alcohol adhesive. At this time, the triacetyl cellulose film was located closer to the polarizer side than the hard coating layer. On the other main surface of the polarizer, the above-mentioned acrylic film was bonded using a polyvinyl alcohol adhesive. Thus, a polarizing film was obtained.
[0307] (Example 1)
[0308] 0.4 parts of the compound (C1), 0.4 parts of the polyether compound (D) (SILYL SAT10 manufactured by Kaneka Co., Ltd.), 0.5 parts of lithium bis(trifluoromethylsulfonyl)imide, 1 part of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), and 0.2 parts of benzoyl peroxide (NYPER BMT manufactured by NOF Corporation) were added to 100 parts of the solid content of the solution of the acrylic polymer (A1) to prepare a solution of an acrylic adhesive composition. SILYL SAT10 is a compound represented by the above formula (13), A 1 is -CH2CH(CH3)-, A 2 -C3H6-, Z 1 -C3H6-Z 0 , reactive silyl group (Z 0 -) is dimethoxymethylsilyl. The number average molecular weight of SILYL SAT10 is 5,000.
[0309] Next, the obtained solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (separator: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with a silicone release agent, and the thickness of the adhesive layer after drying was 20 μm. The coated film was dried at 155° C. for 1 minute to form an adhesive layer on the surface of the separator. Next, the adhesive layer formed on the separator was transferred to one side of the acrylic film of the polarizing film, and a polarizing film with an adhesive layer of Example 1 was prepared.
[0310] (Examples 2 to 12, Comparative Examples 1 to 3)
[0311] Except having changed the composition of the acrylic pressure-sensitive adhesive composition as shown in Table 2, the same method as in Example 1 was carried out to produce pressure-sensitive adhesive layer-attached polarizing films of Examples 2 to 12 and Comparative Examples 1 to 3.
[0312] [evaluate]
[0313] <Weight average molecular weight (Mw) of acrylic polymer and acrylic oligomer>
[0314] The weight average molecular weight (Mw) of the obtained acrylic polymer and acrylic oligomer was measured by GPC (gel permeation chromatography).
[0315] ·Analysis device: Made by Tosoh Corporation, HLC-8120GPC
[0316] ·Pillar: Made by Tosoh Corporation, G7000H XL +GMH XL +GMH XL
[0317] · Pillar size: 7.8mmφ×30cm each, total 90cm
[0318] Column temperature: 40℃
[0319] Flow rate: 0.8ml / min
[0320] Injection volume: 100μl
[0321] ·Eluent: Tetrahydrofuran
[0322] Detector: Differential Refractometer (RI)
[0323] Standard sample: polystyrene
[0324] <Adhesion>
[0325] The adhesive strength P0 and P 85 and P 105The above-mentioned tests 1 to 3 were implemented. The glass with an ITO layer was made by forming an ITO layer on an alkali-free glass (made by Corning, trade name "EG-XG") with a thickness of 7 mm. The ITO layer was made by sputtering. In the ITO layer, the ratio of the weight of Sn atoms to the total value of the weight of Sn atoms and the weight of In atoms (Sn ratio) was 3wt%. For the ITO layer, an atomic force microscope (AFM, made by Bruker, Dimension3100+NanoscopeV) was used to analyze its surface under the following measurement conditions. As a result, the average surface roughness Ra of the ITO layer was 0.2nm, the root mean square average roughness Rq was 0.3nm, and the maximum height Rmax was 2.6nm. The operation of peeling the test piece from the ITO layer was carried out using a tensile testing machine (Autograph SHIMAZU AG-1 1OKN).
[0326] (AFM measurement conditions)
[0327] ·Measurement mode: Tapping mode
[0328] Cantilever: Si single crystal
[0329] ·Measurement area: 10μm square
[0330] <Initial reoperability>
[0331] A reoperation test was carried out using the glass with an ITO layer used in the determination of the adhesive force by the following method. First, a polarizing film with an adhesive layer was cut into strips of 230 mm in length and 120 mm in width to prepare a test piece. Next, the test piece was bonded to the surface of the ITO layer of the glass with an ITO layer through the adhesive layer. The bonding of the test piece to the ITO layer was carried out using a laminator. After the test piece was bonded, it was placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the ITO layer and the adhesive layer, so that the adhesive layer was closely attached to the ITO layer. Next, the test piece was peeled off from the glass with the ITO layer by hand. The reoperation test was repeated three times in the above-mentioned order, and the initial reoperability of the adhesive layer was evaluated according to the following criteria.
[0332] (Evaluation Criteria)
[0333] A: All three films had no paste residue and no film breakage, and could be peeled off well.
[0334] B: The film was broken in some of the three sheets due to peeling, but the sheets could be peeled off by peeling again.
[0335] C: All three sheets had film breakage due to peeling, but could be peeled off by peeling again.
[0336] D: Adhesive residues were found in all three sheets, or the peeling film broke and could not be peeled off no matter how many times the peeling was attempted.
[0337] <Reoperability after preheating>
[0338] In the reoperation test, after the bond between the ITO layer and the adhesive layer was homogenized in an autoclave, a heat treatment was performed in an atmospheric pressure atmosphere at 85°C for 5 hours. After the heat treatment, the test piece was placed in an atmosphere at room temperature to lower the temperature of the test piece to room temperature. In addition, the reoperability of the adhesive layer after preheating was evaluated by the same method as the above-mentioned reoperability evaluation.
[0339] Durability
[0340] A durability test was carried out using the glass with an ITO layer used in the determination of the adhesive force by the following method. First, the polarizing film with an adhesive layer was cut into a strip of 300 mm in length and 220 mm in width as a test piece. Next, the test piece was attached to the surface of the ITO layer of the glass with the ITO layer through the adhesive layer. The attachment of the test piece to the ITO layer was carried out using a laminator. After the test piece was attached, it was placed in an autoclave at 50°C and 0.5MPa for 15 minutes to homogenize the bonding between the ITO layer and the adhesive layer, so that the adhesive layer was closely attached to the ITO layer. Next, the test piece was heat treated for 500 hours in an atmospheric pressure atmosphere at 105°C. The appearance of the adhesive layer between the polarizing film and the ITO layer was observed with the naked eye, and the durability of the adhesive layer was evaluated according to the following criteria.
[0341] (Evaluation Criteria)
[0342] A: There is absolutely no change in appearance such as foaming or peeling.
[0343] B: There is peeling or foaming at the edge, but there is no problem in practical use unless it is used for special purposes.
[0344] C: There is significant peeling at the edge, which is problematic in practical use.
[0345] [Table 2]
[0346]
[0347] The abbreviations in Table 2 are as follows.
[0348] A1: Acrylic polymer (A1)
[0349] A2: Acrylic polymer (A2)
[0350] B1: Acrylic oligomer (B1)
[0351] B2: Acrylic oligomer (B2)
[0352] C1: Compound (C1)
[0353] X-12-967C: 3-Trimethoxysilylpropylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0354] SAT10: SILYL SAT10 (manufactured by Kaneka Corporation)
[0355] X-41-1056: Epoxy-containing oligomer silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0356] According to Table 2, the adhesive layer of the polarizing film with an adhesive layer of the present embodiment maintains reoperability after preheating even when attached to the conductive layer, and has durability in a high temperature environment. It should be noted that in Comparative Examples 2 and 3 in which the compound (C) is not present, it is estimated that the adhesive layer of the polarizing film with an adhesive layer in the present embodiment maintains reoperability after preheating even when attached to the conductive layer, and has durability in a high temperature environment. 85 Under the conditions of , SILYL SAT10 as the polyether compound (D) hardly segregates on the surface of the ITO layer. On the other hand, in the measurement of the adhesive force P 105 Under the conditions of , SILYL SAT10 segregated on the surface of the ITO layer. It can be considered that the adhesion P was obtained in Comparative Examples 2 and 3. 105 Specific adhesion P 85 The result is that the durability after heat treatment at 105°C is low.
[0357] Industrial Applicability
[0358] The pressure-sensitive adhesive layer-attached polarizing film of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic electroluminescent (EL) displays, plasma displays (PD), and field emission displays (FED).
Claims
1. A polarizing film with an adhesive layer, comprising: Polarizing film, and an adhesive layer formed from the adhesive composition, The adhesive composition comprises: a base polymer, a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D), In the adhesive composition, the content of the compound (C) is 0.4 parts by weight or more relative to 100 parts by weight of the base polymer. The adhesive force P of the adhesive layer was determined by the following test 1. 85 The adhesive force P obtained by the following test 2 is 10.0 N / 25 mm or less. 105 Greater than 10.0N / 25mm, Test 1: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 85°C for 5 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 85 ), Test 2: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 105°C for 24 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 105 ).
2. The polarizing film with an adhesive layer according to claim 1, wherein The adhesive force P0 of the adhesive layer obtained by the following test 3 is 10.0 N / 25 mm or less. Test 3: The adhesive layer of the indium tin oxide layer adhered to the glass with an indium tin oxide layer was peeled from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90°, and the force required at this time (adhesive force P0) was measured.
3. The polarizing film with an adhesive layer according to claim 1, wherein The weight average molecular weight of the compound (C) and the number average molecular weight of the polyether compound (D) are each 10,000 or less.
4. The polarizing film with an adhesive layer according to claim 1, wherein The anhydride group is a carboxylic acid anhydride group.
5. The polarizing film with an adhesive layer according to claim 1, wherein The compound (C) further has a silicon atom and a hydrolyzable group bonded to the silicon atom.
6. The polarizing film with an adhesive layer according to claim 5, wherein The content of the hydrolyzable group in the compound (C) is 10 wt % or more.
7. The polarizing film with an adhesive layer according to claim 1, wherein The compound (C) has a siloxane bond.
8. The polarizing film with an adhesive layer according to claim 1, wherein The polyether compound (D) further has a silicon atom and a hydrolyzable group bonded to the silicon atom.
9. The polarizing film with an adhesive layer according to claim 8, wherein The content of the hydrolyzable group in the polyether compound (D) is 14 wt % or less.
10. The polarizing film with an adhesive layer according to claim 1, wherein The adhesive composition includes a (meth)acrylic polymer (A) as the base polymer.
11. The polarizing film with an adhesive layer according to claim 10, wherein The (meth)acrylic polymer (A) has an acidic group.
12. An image display panel comprising: The polarizing film with an adhesive layer according to any one of claims 1 to 11, A conductive layer comprising a metal oxide, and transparent substrate, in, The adhesive layer is directly in contact with the conductive layer.
13. The image display panel according to claim 12, wherein: The metal oxide includes indium tin oxide.
14. The image display panel according to claim 12, wherein: The adhesive layer comprises a first layer containing the compound (C) or a reactant thereof, and a second layer containing the polyether compound (D) or a reactant thereof, The conductive layer, the first layer, and the second layer are arranged in this order in a stacking direction.
15. The image display panel according to claim 14, wherein: The adhesive layer further comprises a third layer comprising a (meth)acrylic polymer (A) or a reactant thereof, The third layer is located between the second layer and the polarizing film.
16. A method for manufacturing an image display panel, which is the method for manufacturing an image display panel according to any one of claims 12 to 15, the method comprising: The pressure-sensitive adhesive layer is subjected to a first heat treatment at 70° C. to 95° C. in a state where the pressure-sensitive adhesive layer-attached polarizing film is attached to the conductive layer.
17. The method for manufacturing an image display panel according to claim 16, further comprising: After the first heat treatment, the pressure-sensitive adhesive layer is subjected to a second heat treatment at a temperature higher than 95°C.
18. An adhesive layer formed from an adhesive composition, The adhesive composition comprises: a base polymer, a compound (C) having an acidic group or an acid anhydride group, and a polyether compound (D), In the adhesive composition, the content of the compound (C) is 0.4 parts by weight or more relative to 100 parts by weight of the base polymer. The adhesive force P obtained by the following test 1 85 The adhesive force P obtained by the following test 2 is 10.0 N / 25 mm or less. 105 Greater than 10.0N / 25mm, Test 1: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 85°C for 5 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 85 ), Test 2: The adhesive layer of the indium tin oxide layer attached to the glass with the indium tin oxide layer was heated at 105°C for 24 hours, and the force required to peel the adhesive layer from the indium tin oxide layer at a peeling speed of 300 mm / min and a peeling angle of 90° (adhesive force P 105 ).
Citation Information
Patent Citations
Hakumakujinkohenkomakuno seiho
JP1976069644A
Directional control method of fold printed matter
JP1985071459A
Polarizing plate and its production
JP2000338329A
Manufacturing method of optical film laminate including thin and high-functional polarizing film
JP2012073563A
Acid anhydride group-containing organosiloxane and method for producing the same
JP2013129691A